Dynamic remodeling of pipe material interfacial properties: Intervention effects on biofilm in water distribution networks and multi-omics insights - Jingna Zhang; Wencheng Ma; Yu Ouyang; Dan Zhong; Pengyuan Cheng; Jun Ma (Water Research, 2027)

Identification of citrus commercial varieties with pattern decoupling representation learning - Xinlong Wen; Zian Wang; Qiang Wang; Bo Zhang; Dan Wu; Jason Sun; Wei Song; Rongbo Zhu; Yunjiang Cheng (Food Control, 2026)

Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Profiling structural variations of the α-globin gene cluster by the single molecule real-time sequencing: remarkable diversity of the spectrum with rare and novel variants identified in a large Chinese cohort - Dan Wei; Zifeng Cheng; Wei Wei; Chunrong Gui; Juliang Liu; Hongfei Chen; Yunting Ma; XianWei Peng; Dan Yu; Yan Huang; Yinghui Lai; Baoheng Gui (Human Genetics, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Post-stroke endothelial cell plasticity: A transformational lineage from complete to partial EndoMT - Siyi Tang; Cheng Li; Zhijun Yu; Dan Shu; Li Chen; Qiong Yuan (Tissue and Cell, 2026)

Mesozoic crustal thinning in the northern North China Craton: Evidence from Triassic and Jurassic plutons in the Huyu area, northwestern Beijing - Liang Qiu; Dan-Ping Yan; Jun-Ting Qiu; Wei Yang; Yiyu Lin; Suhua Cheng; Xiuhua Cao; Xuchao Chai; Pei Zhang; Lei Gao; Zeyilin Ma (Journal of Asian Earth Sciences, 2026)

Management and reshaping of urban water supply systems: perspectives from carbon emission reduction - Yisong Zhu; Wencheng Ma; Yu Ouyang; Rui Fang; Chengzhi Zheng; Dan Zhong; Pengyuan Cheng (Sustainable Cities and Society, 2026)

Allelochemicals stimulation (ACS) strategy: Potential for studying allelopathy and discovery of phytotoxins - Dan He; Zhibo Hu; Haishan Cui; Cheng Li; Qiang Wang; Heng Guo; Lan Liu; Jing Li (Phytochemistry, 2026)

Ganocochlearcins A-P: Acyclic meroterpenoids from Ganoderma mushrooms targeting extracellular matrix remodeling in cancer-associated fibroblasts - Fu-Ying Qin; Dan Cai; Jiao-Jiao Zhang; Zhi-Yu Chen; Yong-Xian Cheng (Phytochemistry, 2026)

A multi-scale SDP and enhanced RepViT-based method for ship shaft-rate magnetic field signal detection - Ye Wang; Zhentao Yu; Cheng Chi; Jianxin Pei; Bozhong Lei; Dan Wang (Ocean Engineering, 2026)

A mitochondria-targeted fluorescent probe for monitoring of H2O2 and polarity/viscosity-related microenvironmental changes in food mycotoxin- and environmental contaminant-induced hepatotoxicity - Zibo Zhai; Jia Huang; Xijian Wang; Hailin Zhang; Min Deng; Qiqi Wen; Jingting Fang; Lizi Liu; Ziyang Ding; Dan Cheng; Longwei He; Songjiao Li (Journal of Environmental Chemical Engineering, 2026)

A coordination framework between drinking water treatment plants and water distribution networks for dynamic risk threshold identification - Dan Zhong; Chaoyuan Huang; Pengyuan Cheng; Wencheng Ma; Rongxing Ma (Journal of Environmental Chemical Engineering, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Flavoromics and machine learning for baijiu flavor and quality prediction - Dan Zheng; Tao Sun; Cheng Fang; Changliang Yao; Tianlu Chen; Aihua Zhao; Yan Xu; Wei Jia (Food Chemistry, 2026)

Sub-nanometer FeNi proximity steers target-specific decontamination via d-d orbital coupling-induced PMS activation - Yaqi Yin; Shugang Zheng; Zengmei Zhu; Laijing Xie; Dan Feng; Yunqing Liu; Weihong Chen; Dayi Qian; Jiangwei Shang; Xiuwen Cheng (Chemical Engineering Journal, 2026)

Mechanistic insights into selective and pH-independent removal of sulfamethazine by Fe2O3-functionalized lignin-derived biochar - Xueping Sun; Haitao Sheng; Xiaoyu Zhang; Xiangxue Chen; Xinbai Jiang; Cheng Hou; Jinyou Shen; Dan Chen (ENGINEERING Environment, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Lucidumones L-P: Meroterpenoids from Ganoderma lucidum and their inhibitory effect on triple negative breast cancer - Jiao-Jiao Zhang; Ze-Hong Wu; Yuan-Nan Yuan; Dan Cai; Jia-Wang Liu; Hong Zhou; Zhong-Hui Yang; Yan-Jiao Yin; Yong-Xian Cheng (Phytochemistry, 2026)

Mitigate dynamic response analysis of submerged floating tunnel (SFT) under wave and impact loads - Xiaolu Cui; Lihua Wang; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Tracing the evolutionary history of small HERCs reveals an unprecedented expansion in fish related to virus infection - Meng-Yao Wu; Xiu-Ying Gong; Wen-Hao Guo; Hong-Yu Luan; Zhen-Yang Zhao; Cheng Dan; Yi-Bing Zhang (Fish & Shellfish Immunology, 2026)

Screening of immune adjuvants for an attenuated live vaccine derived from the Aeromonas veronii TH0426 strain with a hisJ gene deletion and evaluation of its immune protection in crucian carp - Qixing Huang; Ruitong Li; Shuoyu Wang; Ruiqi Liang; Peiqi Lu; Bingmei Du; Yan Cheng; Xiaochen Ren; Jinhong Li; Xu Dong; Jiaojiao Yang; Luyao Chu; et al. (Fish & Shellfish Immunology, 2026)

Dynamic monitoring of sleeper strain and ballasted support condition based on embedded fiber-reinforced polymer–optical fiber sensing rebar - Cheng Chen; Peigang Li; Zexu Zhao; Meng Hu; Caihao Lan; Dan Li; Yutong Liu (Engineering Structures, 2026)

Recent advances and applications in integrated passive microfluidic platforms for circulating tumor cell detection - Zhengxian Dan; Ziwen Cheng; Chen Huang; Shijie Qu; Xinyi Wang; Huanhuan Shi (Chemical Engineering Journal, 2026)

High-permeability nanophotosensitizer eliminates biofilm-associated infection through concurrent lipid peroxidation and extracellular DNA degradation - Xiaochun Xie; Ziming Huo; Shaowen Wang; Jiying Liu; Chenyang Guo; Huantai Luo; Chuanxu Cheng; Wen Sun; Shan Guan; Panpan Chang; Dan Shao; Ronghua Yang (Chemical Engineering Journal, 2026)

Electrospun nanofibrous film co-loaded with thymol/thiabendazole hydroxypropyl-β-cyclodextrin inclusion complexes: humidity-triggered release and edible fungi preservation application - Xinran Yin; Dan Zhu; Xinyan Zhang; Ruiwen Cheng; Haonan Ren; Yanan Sun; Demei Meng; Weina Li; Fansheng Cheng (Chemical Engineering Journal, 2026)

Application of the RIPB approach in the aqueous homogeneous reactor - Zhiqiang Zou; Dan Zhang; Ningning Wang; Zhengyu Du; Shuwen Yu; Shisi Cheng; Chunrui Deng; Liping Wu (Annals of Nuclear Energy, 2026)

MATHFI: A Multi-scale Adaptive Thresholding and Hierarchical Feature Integration Network for Retinal Vessel Segmentation and Quantitative Biomarker Analysis - Michelle N. Tolentino; Stephen Lloyd C. Abenoja; Jonathan C. Morano; Dan Michael A. Cortez; Ymir M. Garcia; Kuo-Sheng Cheng (Journal of Medical and Biological Engineering, 2026)

Antidepressant effects of Gardeniae Fructus on chronic unpredictable mild stress model mice: involvement of DNMT3B-mediated epigenetic regulation of GR in the prefrontal cortex - Lu-Lu Zhang; Xiao-Wei Wang; Yi-Dan Cheng; Ya Liu; Hesham R. El-Seedi; Peng-Cheng Sun; Wen-bin He; Jian-Jun Zhang; Zhi-Guang Zhai (Journal of Natural Medicines, 2026)

Stratospheric intrusion and deep boundary layer coupling drive surface ozone bursts over the Southern Tibetan Plateau during the monsoon season - Ying Shen; Dan Li; Zhixuan Bai; Yinghong Wang; Mengtian Cheng; Yu Wang; Yang Zhang; Deqing Zhuoga; Nima Chuduo; Yaoming Ma; Jianchun Bian; Yuesi Wang; et al. (Science Bulletin, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Coupled vibration characteristics and vibration mitigation of submerged floating tunnel-track-train under wave load - Xiaolu Cui; Lihua Wang; Ke Li; Wenlong Luo; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Tailoring NiFe LDH with ruthenium doping for high-performance bifunctional electrocatalysis in conventional and environmental water splitting systems - Jiarun Cheng; Chaojie Lyu; Jiaxin Yang; Senlong Zhang; Xueyan Li; Dan Zhang; Yiming Liu (Fuel, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Effects of different processing methods on bioaccessibility of phenolic compounds in flaxseed meal - Lin Cheng; Mengjiao Zhao; Hongtao Guo; Yongxia Cheng; Yue Shen; Dan Hai; Lianjun Song; Yinping Wang; Guangshan Zhao; Xianqing Huang; Yan Ma (Food Chemistry, 2026)

TLR4 knockout ameliorates acute LPS-sensitized tolvaptan-induced idiosyncratic liver injury by disrupting drug metabolism, inflammation, and bile acid homeostasis - Xin Jiang; Yi-xin Hu; Bing-yu Cheng; Jing-wen Hu; Yu-qing Zhao; San-lan Wu; Heng Li; Li-Meng Gong; Guang Feng; Dan Li; Lu-qin Si; Jian-geng Huang (Food and Chemical Toxicology, 2026)

Synchronously enhanced methanogenesis performance and reduced antibiotic resistance genes of cattle manure anaerobic digestion by air nanobubble water - Jiabei Shan; Tianfeng Wang; Cheng Peng; Peilin Guo; Hong Zhu; Dan Luo; Yonggang Wang; Jixiang Chen (Bioresource Technology, 2026)

Soybean MYB transcription factors GmMYB73 and GmMYB85 regulate lipid biosynthesis through lncRNA-mediated mechanisms - Jiaxin Wang; Xingyu Guo; Yanqiu Li; Xinchao Luan; Yushan Bai; Lianjie Li; Peiwu Wang; Jian Wei; Wenge Cheng; Wenyuan Hao; Dan Yao (Theoretical and Applied Genetics, 2026)

ABI5-activated ALKBH10B demethylates RAP2.6 mRNA to modulate Arabidopsis salt tolerance - Shurong Xuan; Mengxue Cheng; Yunze Wen; Qiang Wei; Dan Zhang; Peng He; Jianing Yu (Plant Cell Reports, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

LncRNA TRHDE-AS1 functions as a tumor suppressor in ovarian cancer via the miR-17-5p/PIK3R1 ceRNA regulatory axis - Hui Liu; Chengwen Song; Dan Cheng; Jianhua Sun; Chuchao Zhu; Yuan Huang (Journal of Molecular Histology, 2026)

Two new protoflavonoids from Polytrichum commune and their cytotoxicity against human gastric cancer cells - Jing-jing Dong; Dan-rui Han; Hao Cheng; Xu-liu Shi; Dong-Lai Ma; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

First report of Fusarium asiaticum causing stem rot on pitaya in China - Dan Lei; Xueying Shang; Zhu Li; Kun Guo; Ziqin Bai; Geng Liu; Qing Tan; Jieyu Li; Chenlan Li; Li Cheng; Hui Luo (Crop Protection, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Elevated suspended particulate matter reorganises carbon fraction in mangrove ecosystems - De Cheng; Dan Li; Shengfa Yang; Xu Zhang; Qin Zhang; Jia Li; Jie Liu; Yufeng Mao; Yi Xiao (Marine Environmental Research, 2026)

Decoding molecular switches mediating uranium speciation transition in iron-based mineral dynamic phase evolution - Bin Xie; Dun Wei; Qiong Tian; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Journal of Hazardous Materials, 2026)

Convergent shifts in microbial communities: Petroleum hydrocarbon contamination suppresses matrix heterogeneity - Wenjuan Jia; Jingcheng Li; Kai Wang; Lirong Cheng; Naifu Jin; Qing Yang; Dan Zhang; Xuefeng Xia; Nuchao Xu; Mingming Wang; Jin Meng; Yi Zhu; et al. (Journal of Hazardous Materials, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

Quercetin-lysozyme complex as a novel wall material for microencapsulation of DHA algal oil: Molecular Dynamics、Structural characterization and antioxidant capacity - Lili Liu; Shuhang Ju; Dan Li; Weiwei Cheng; Xinshuai Zhang; Li Hu (Food Bioscience, 2026)

Probabilistic predictions of the impacts of climate warming on permafrost stability along the Qinghai-Xizang Railway, China - Chengsong Yang; Guodong Cheng; Wei Wei; Lin Chen; Wenqiang Zhang; Xinbin Wang; Qihao Yu; Dan Wang (Cold Regions Science and Technology, 2026)

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

Interaction effects and legacy effects of multiple environmental stressors on rice growth and the rhizosphere microbiome - Yifan Zhao; Shuxun Cheng; Rujiong Zeng; Zhiqi Hong; Dan He; Caixian Tang; Zhongmin Dai (Applied Soil Ecology, 2026)

Long-term N fertilization altered viral community composition and increased functional potentials of phosphorus cycling by causing soil acidification - Shuxun Cheng; Zhongmin Dai; Dan He; Ran Xue; Kankan Zhao; Jorge L. Mazza Rodrigues; Lucas W. Mendes; Scott X. Chang; Jianming Xu (Soil Biology and Biochemistry, 2026)

Coupled dynamics and resonance mitigation of submerged floating tunnel roadways under transient impact loads in marine environments - Xiaolu Cui; Jing Chen; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong; Pupeng Ai; Shixiao Fan (Ocean Engineering, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Nanobubble-mediated high-density growth and enzyme activity enhancement of petroleum degrading bacterium Rhodococcus erythropolis KB1: Mechanism and application - Tianfeng Wang; Yuxin Zhang; Hong Zhu; Zixuan Wang; Cheng Peng; Yuqian Zhang; Ziying Xu; Dan Luo; Yonggang Wang; Jixiang Chen; Wei Peng (Journal of Hazardous Materials, 2026)

CO2-responsive ethyl cellulose–microsphere films for postharvest freshness monitoring of fresh products - Daoyu Liu; Liangbin Hu; Enbo Xu; Huan Cheng; Hongbo Li; Dan Xu; Jiayi Zhang; Lishan Yao; Lu Tian; Xiaolin Zhu; Feilei Zhu; Jing Wang; et al. (Food Control, 2026)

Breaking oxidative interference: Electro-induced uranium incorporation into magnetite for nitrate‑uranium co-contaminated wastewater remediation - Dixiao Xu; Qiong Tian; Dun Wei; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Desalination, 2026)

Volcanic source change triggers divergent climatic responses across the Guadalupian–Lopingian transition in eastern South China - Cheng Cheng; Dan Wang; Shuangying Li; Hua Zhang (Earth and Planetary Science Letters, 2026)

Thermal-cyclized polyacrylonitrile binders enable robust electrode–electrolyte interfaces for designing stable microscale SnO2 anodes - Zehua Chen; Yina Lian; Ting Wang; Dan Cheng; Chuanhong Wang; Yaochun Liu; Yuan Liu (Chemical Engineering Journal, 2026)

Multifunctional LiSCN modified SnO2 electron transport layer for efficient and stable n-i-p perovskite solar cells - Liang Lei; Song Zhang; Ting Zhu; Cheng Gao; Yafei Liu; Zhangbo Lu; Zhitao Shen; Ming Li; Dan Chi; Jianlong Kou; Shunchang Liu; Shihua Huang (Chemical Engineering Journal, 2026)

Decreased gelatinization and retrogradation promoting cold storage stability in glutinous rice via low SSIIa activity-mediated structural modifications of amylopectin - Cheng Liang; Dan Liu; Yuesi Bu; Chiyu Wang; Chunyan Jiang; Xuemei Ma; Xueying Zhang; Tian Hu; Xunchao Xiang; Yungao Hu; Liang Xu (Carbohydrate Polymers, 2026)

Ball-milled biochar stabilizes antimony in contaminated soils by driving rhizosphere metabolite-bacteria synergy - Gratien Twagirayezu; Hongguang Cheng; Antong Xia; Zhibing Wu; Mohamed Abo-Eldahab; Dan Xing; Deng Linbo; Yanyou Wu (Biomass and Bioenergy, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

Comprehensive Analysis of Mixed Reproductive Health Effects of Neonicotinoids: Association with Declining Sperm Concentration and Total Sperm Count in Men - Ruyun Liu; Xun Li; Yilin Xue; Xuanxuan Wang; Cheng Wang; Shulin Yang; Tao Zhang; Dan Hu; Si Liu; Jing Yue; Lei Jin; Ke Gao; et al. (Exposure and Health, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Correction: Associations Between Dietary Selenium Intake and Risk of Incident Arthritis: Based on UK Biobank WebQ Assessment (2009–2012) - Xuena Yang; Chen Liu; Jin Feng; Shiqiang Cheng; Chuyu Pan; Wenming Wei; Dan He; Boyue Zhao; Jingni Hui; Li Liu; Yan Wen; Yumeng Jia; et al. (Biological Trace Element Research, 2026)

Polyketide production in a mangrove-associated fungus Diaporthe goulteri , induced by chemical epigenetic modification - Xiaolin Ma; Xia Wei; Shangping Xing; Xue Cheng; Junfei Lu; Chunxia Yang; Genshi Zhao; Ziteng Dai; Shiyu Hou; Yanying Liu; Dan Zhu (Natural Product Research, 2026)

Electroacupuncture mitigates cognitive impairment caused by anesthesia and surgery in aged rats by inhibiting the p38 MAPK signaling pathway - Bin Cheng; Qian He; Dan Ge; Shuyan Ma; Yuyu Luo; Jiao Wang (Neurotoxicology and Teratology, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Elucidating the pyrolytic mechanisms of clean and safe gas generator 5-amino-1H-tetrazole/SiO2: A comprehensive kinetic and theoretical investigation - Si-Yuan Zhou; Xuan Li; Yuan-Hui Liu; Hao-Tian Zhou; Peng-Cheng Xi; Dan Zhang; Mi Li; Li-Feng Xie (Fuel, 2026)

Ecological processes in microbial community time series during sauce-flavor baijiu fermentation - Shiyuan Ma; Yadong Zhang; Yiyang Zhou; Zhongfu Duan; Dan Huang; Ping Huang; Jiao Niu; Wei Cheng; Chongde Wu (Food Research International, 2026)

Achieving reversible dispersion and facile modification of dried cellulose nanocrystals using polyethylene glycol dimethyl ether as a superior capping agent - Yue Niu; Lulu Fu; Kaijie Liu; Huiqing Liu; Dan Zhang; Aoran Wang; Hongxiang Xie; Zhi Fan; Minjie Guo; Bowen Cheng (Food Hydrocolloids, 2026)

Amino-modified polystyrene nanoplastics induce endothelial pyroptosis and pro-atherogenic cellular responses - Junliang Chen; Ye Cheng; Jining Wang; Xiaodan Sun; Le Wang; Dan Liu; Xiangyu Cao (Food and Chemical Toxicology, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Intelligent prediction of rock-like material strength based on RGB information from borehole imaging - Dan Gao; Zhongwen Yue; Wei Liu; Zifan Cheng; Tianci Li; Di Shu; Mengjia Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Associations between Dietary Selenium Intake and Risk of Incident Arthritis: Based on UK Biobank WebQ Assessment (2009–2012) - Xuena Yang; Chen Liu; Jin Feng; Shiqiang Cheng; Chuyu Pan; Wenming Wei; Dan He; Boyue Zhao; Jingni Hui; Li Liu; Yan Wen; Yumeng Jia; et al. (Biological Trace Element Research, 2026)

Seneca Valley virus 2B and 3 C proteins attenuate the cGAS-STING signaling pathway by targeting STING for degradation - Xuexia Wen; Meijun Zhou; Shijie Xie; Jin Yuan; Yu Hong; Ruiyi Ma; Liwei Zhao; Dan Wang; Rong Quan; Peipei Cheng; Jiangwei Song (Veterinary Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Fungal diversity drives soil health and agricultural sustainability in black soils - Teng Yang; Xu Liu; Leho Tedersoo; Xiyuan Xu; Guifeng Gao; Kunkun Fan; Luyao Song; Dan Zhao; Yuying Ma; Li Nie; Di Wu; Jingjing Liu; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Optimization of Valve-Closing Rules Based on Genetic Algorithms during water hammer - Dan Jiang; Cheng Yue; Yuanming Liu; Qing Guo (Journal of Water Process Engineering, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Ginkgo leaf-derived Co3O4/N-doped biochar for enhanced rapid degradation of tetracycline in water via peroxymonosulfate activation - Ting Shen; Ao Cheng; Dong Chen; Dan Wang; Yafei Zhao; Bing Zhang (Journal of Environmental Chemical Engineering, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Two Bacillus strains as a composite microbial inoculant enhance degradation of polylactic acid plastics in composting - Tianfeng Wang; Yuqian Zhang; Huiping Zhou; Xiangting Shi; Yuxin Zhang; Zhenkai Li; Cheng Peng; Yonggang Wang; Dan Luo; Xuemei Zhang; Jining Zhang; Liqing Xin (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into uranium release during long-term structural evolution of uranium-doped magnetite - Wei Xu; Qiong Tian; Dun Wei; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Journal of Environmental Sciences, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Physicochemical properties of edible oxidized gum arabic–polylysine crosslinked films and their effects on the postharvest preservation of litchi - Dan Li; Huirong Cheng; Ling Xie; Hong Luo; Dandan Zhang; Jupeng Zhao; Yueming Jiang; Liang Gong (Postharvest Biology and Technology, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Advances in Calotropis gigantea Linn.: from phytochemistry and biological activities to diverse applications - Guo-Qing Chen; Xin-Ying Wu; Yun-Cheng Huang; Jian-Ming Jiang; Shun-Yuan Guo; Jia-Hong Chen; Zhen-Dan He; Xun Song (Next Research, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Efficient degradation and detoxification of quinolone antibiotics using the novel biocatalyst BpLac@IPM - Hongjuan Zhu; Dan Zhou; Bianxia Li; FanYang; Yujie Chen; Jiashu Liu; Wanli Cheng; Huanan Li; Zhengbing Jiang (Journal of Water Process Engineering, 2026)

Fluid flow and heat transfer during staged multi-cluster fracturing treatments along horizontal wells — Application for hydraulic fracture characterization using distributed temperature sensing - Cao Wei; Dan Qu; Haitao Li; Shiqing Cheng; Chang Liu; Hassan Hassanzadeh (Geothermics, 2026)

Soil bacterial community and vanadium fate shaped by co-exposure to polyethylene microplastics and native vanadium pollution - Shanshan Zhao; Lan Li; Jianing Sun; Jingyu Hu; Wu Liu; Xin Cheng; Dan Zhou; Bo Cheng (Applied Soil Ecology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Study on the ignition and hydrogen evolution characteristics of wet magnesium powder under strong ignition conditions - Qi Jing; Wanyun Chen; Zhiyuan Yang; Dan Wang; Zhou Wang; Lei Cheng; Yuntao Li (Fuel, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

Molecular sensomics reveal the cultivar dependence and seasonal dynamic mechanism behind the unique aroma of Wuyuan green tea - Cuinan Yue; Xiaoqun Xie; Meihong Yan; Luo Li; Sibin Wang; Yajing Wan; Dan Cheng; Lizhen Chen; Lifang Zou; Wenjin Li; Zhihui Wang (Food Chemistry, 2026)

Lactic acid bacteria in Jiangxiangxing Baijiu fermentation: Resource exploration, community succession and their ecological dynamics - Pan Huang; Zhongfu Duan; Shiyuan Ma; Wei Cheng; Qiuxia Li; Dan Huang; Ping Huang; Rongqing Zhou; Jiao Niu; Yadong Zhang; Chongde Wu (Food Bioscience, 2026)

Z-scheme ZnFe2O4/MoO3 composite as efficient peroxymonosulfate activator under visible light for enrofloxacin degradation - Dan Feng; Tianning Zhang; Shugang Zheng; Shihu Cao; Wenyao Zhang; Jiangwei Shang; Nasen Bate; Xiuwen Cheng (Environmental Research, 2026)

Green carbon quantum dot films derived from banana leaves with efficient luminescent spectral conversion for high-performance solar cells - Zengwu Ma; Busheng Zhang; Hongming Chen; Fanqin Yue; Linyu Cheng; Woon-Ming Lau; Dan Zhou (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Shaft-Rate Magnetic Field Localization Algorithm Based on Improved Exponential Triangular Optimization - Bozhong Lei; Ranfeng Wang; Cheng Chi; Lu Yu; Zhentao Yu; Dan Wang (Journal of Marine Science and Engineering, 2026)
Addressing the issues of low positioning accuracy and poor robustness in shaft-rate magnetic fields, this study introduces the Improved Exponential Triangular Optimization Algorithm (IETO). By incorporating adaptive attenuation factors, dynamic population reduction, and intelligent boundary contraction strategies, it significantly enhances the global search capability and robustness. A magnetic dipole localization model is developed, and comparative simulations show that IETO achieves reliable accuracy and robustness under low signal-to-noise ratio (SNR) conditions, reducing localization error by 7.82% compared with the conventional Exponential Triangular Optimization Algorithm (ETO). The effects of base station deployment, number of stations, and sea depth on localization performance are further examined, and the capability of IETO for dynamic target tracking is verified. Preliminary sea trial results confirm the practical feasibility and engineering applicability of the proposed method.

Cordyceps militaris polysaccharides improved tomato postharvest disease resistance - Hongyong Zhang; Tianhao Li; Xingchi Ma; Peng Zhao; Xia Gao; Yanan Sun; Shuliang Zhang; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Machine learning-based rapid assessment of wave attenuation performance: A random forest approach for breakwater monitoring - Xiaofei Cheng; Junnan Wang; Dan Wu; Mingyu Yan; Chenhan Xu (Ocean Engineering, 2026)

Unraveling the synergistic impact of calcium ions and pH on the rejection of per- and perfluoroalkyl substances by nanofiltration in complex water matrices - Caihong Liu; Xinyi Cheng; Jingjun Bo; Rui Gao; Ye Shen; Yue Zhi; Dan Song; Qiang He (Journal of Hazardous Materials, 2026)

Cyprinid fish ubiquitin-specific protease 18 (USP18) downregulates the basal and induced interferon expression - Ji-Cheng Yu; Wen-Hao Guo; Xiu-Ying Gong; Hong-Yu Luan; Meng-Yao Wu; Zhen-Yang Zhao; Cheng Dan; Yi-Bing Zhang (Fish & Shellfish Immunology, 2026)

From waste to wellbore reinforcement: Assessment of quartz tailings functionalization in oil well cement under simulated HTHP conditions - Feng Zhao; Xueling Zeng; Dan Long; Kaiyuan Mei; Chunmei Zhang; Gaoyin Zhang; Xiaowei Cheng (Environmental Research, 2026)

Novel electrochemical reactor for accelerated uranium mineralization: Enabling continuous and rapid uranium wastewater treatment - Dan Huang; Lanlan Cao; Xiaoyan Wu; Zhaowen Cheng; Qiong Tian; Dun Wei; Qi Fang; Tao Cai; Xiaowen Zhang; Yilong Hua; Mi Li (Desalination, 2026)

Signaling pathways and potential therapeutic agents in trastuzumab-induced cardiotoxicity - Haonan Zhang; Changxu Lu; Siyuan Cheng; Jingyi Wu; Anqi Hu; Zhongyi Mu; Dan Dong; Mingli Sun (Apoptosis, 2026)

Stressor Combinations Shift Soil Microbial Communities From Rare to Unknown Taxa and Alter Genomic Strategies - Shuxun Cheng; Xianjin Tang; Xing Huang; Yang Li; Shuyi Huang; Dan He; Eduardo Moreno‐Jiménez; Jianming Xu; Matthias C. Rillig; Zhongmin Dai; Manuel Delgado‐Baquerizo (Global Change Biology, 2026)
Soil microorganisms constitute the largest portion of Earth's biodiversity. However, soil microorganisms are also highly sensitive to on‐going global change, and the influence of an increasing number of stressors on common, rare, and unknown taxa across large environmental gradients remains virtually unknown. Here, we combined a large‐scale spatial field survey across multiple different ecosystems and found that the diversity and abundance of soil rare taxa were significantly reduced under high environmental stressor number (i.e., a high number of stressors passing a 75% stressor threshold). Strikingly, the abundance of unknown soil taxa and unknown genes increased with increasing environmental stress number. We further identified the metagenome‐assembled genomes (MAGs) that were considered as relatively common taxa using metagenomics. Compared to 9% of negative responders, 32% of common MAGs were resistant or positively responsive to multiple stress, displaying a reduced potential for cellular processes and an enhanced potential for environmental, genetic, and metabolic processes. Our study suggests that as stress increases, we would have less rare, but more unknown microorganisms and unique genomes of resistant common taxa, suggesting major changes in the soil microbiome in a world subjected to multiple global change stressors.

The role of amino acid signaling in pathogenesis of chronic kidney disease - Siya Yan; Xiangqi Zhang; Ruizhen Bu; Ge Li; Yang Wang; Meifang Cheng; Qian Chen; Yuzheng Wu; Yi Zhang; Dan Wang; Tao Wang (Molecular and Cellular Biochemistry, 2025)

Differential cannabinoid-like effects, receptor affinity and physiologically based pharmacokinetics of the synthetic cannabinoids 4F-MDMB-BINACA, 4F-MDMB-BICA and 5F-MDMB-PICA in mice: A comparative study - Yawen Xu; Simeng Zhang; Xuesong Shi; Lixin Kuai; Yuanyuan Chen; Kaixi Li; Xiangyu Li; Yanling Qiao; Dan Wang; Cheng Jiang; Peng Xu (Toxicology and Applied Pharmacology, 2025)

Spirocyclic polyketide analogues from the endophyte fungus Penicillium sp. YUD25002 associated with Panax notoginseng - Wen-Jing Wang; Ju-Cheng Zhang; Yan Geng; Hai-Xia Dong; Fei Xie; Tian-Peng Xie; Zhi-Feng Zi; Dan-Dan Xia; Han-Jue Zhang; Hao Zhou; Min Yin; Zhong-Tao Ding (Phytochemistry Letters, 2025)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

The study of stiffness design of tube, cable, and joint in submerged floating tunnel by segmentation analysis method under static and dynamic loads - Jie Hou; Bo Huang; Linzhong Han; Peng Chen; Hao Ding; Jianting Zhou; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Pulsed volcanism in the Emeishan Large Igneous Province drove deglaciation during the Guadalupian-Lopingian transition - Cheng Cheng; Hua Zhang; Dan Wang; Shuangying Li; Shuzhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Improving polylactic acid plastic biodegradation under thermophilic anaerobic conditions using nanobubble water - Tianfeng Wang; Peilin Guo; Qianqian Zheng; Cheng Peng; Jiazi Niu; Jie Wang; Dan Luo; Yonggang Wang; Jixiang Chen (Journal of Environmental Chemical Engineering, 2025)

Ultrahigh-stability Co3O4/CuO hetero-nanoarrays with multi-oriented architecture for cascade nitrate reduction in neutral media - Yuanyuan Zhao; Yinze Yang; Ao Cheng; Ting Shen; Dan Wang; Yafei Zhao; Huishan Shang; Bing Zhang (Journal of Environmental Chemical Engineering, 2025)

Flame characteristics and explosion risk of hydrogen-blended natural gas pipeline leakage under high-pressure and high-equivalence-ratio environments - Sheng Qi; Yuntao Li; Wenhao Zhang; Dan Wang; Rui Zhou; Qi Jing; Lei Cheng; Zhou Wang (Fuel, 2025)

Lactylation-related multigene signature in multiple myeloma: integrated prognostic stratification, immune landscape profiling, and therapeutic guidance - Wuyang Zhang; Shuai Ming; Peng Cheng; Dan Shi; Jingyu Li; Bin Wang; Yu Fang; Mengru Li; Wei Cao; Min Wang; Zaibao Wang; Jiawei Xiao; et al. (Immunologic Research, 2025)

Microglial Necroptosis Mediated by RIPK3 Leads to Retinal Ganglion Cell Apoptosis Through the Release of FGF2 After Ischemia/Reperfusion - Jian Liu; Anping Ma; Guangyi Huang; Wen Hu; Xin Xu; Rong Huang; Yaguang Hu; Qiaochu Cheng; Yanlin Feng; Dan Ye; Fan Xu; Aimin Sang (Journal of Molecular Neuroscience, 2025)

Divergent responses of cropland soil available potassium to fertilization across the Sichuan Basin of China - Jinli Cheng; Dan Chen; Xinyi Chen; Yaruo Mao; Aiwen Li; Ke Zhu; Yaling Yu; Wanqi Tan; Bing Li; Bin Zhao; Qiquan Li (Soil and Tillage Research, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Determining the differences in O3-NOx-VOCs sensitivity between sauna and roast days - Yuting Liu; Yinghong Wang; Yusi Liu; Mengtian Cheng; Baoxian Liu; Tao Song; Bo Hu; Dan Yao; Miao Yu; Yu Shi; Guiqian Tang; Yuesi Wang (Journal of Environmental Sciences, 2025)

Development and quality analysis of low GI composite buckwheat steamed bun - Ting Zhang; Jiayue Zhang; Wanzeng Li; Xinyuan Hu; Huiru Cheng; Kang An; Jingwen Wang; Dan Yang; Hua Li; Jun Xi; Kunlun Liu; Zhifeng Zhang; et al. (Journal of Cereal Science, 2025)

Anthropogenic activities regulate the assembly strategy of conditionally rare taxa in airborne microbial communities - Yuanyuan Pan; Xin Ke; Dan He; Renguo Zhu; Cheng Liu; Caixia Hu (Atmospheric Pollution Research, 2025)

A pectin methylesterase inhibitor NtPMEI21 negatively regulates resistance to brown spot disease in Nicotiana tabacum L. - Yalin Bai; Yan Ji; Zipeng Jiang; Zunqiang Li; Zhengwen Liu; Qiang Zhang; Yu Zhang; Caihong Jiang; Aiguo Yang; Lirui Cheng; Dan Liu (Plant Science, 2025)

Highly efficient (Au)(III) recovery from acid wastewater by thiosemicarbazide modified Zr-MOF - Guowen He; Dan Wu; Dechong Ma; Jiaqi Bu; Zecheng Cheng (Journal of Water Process Engineering, 2025)

Response of formaldehyde to meteorology in Beijing: Primary or secondary contributions - Yanyu Kang; Yinghong Wang; Mengtian Cheng; Baoxian Liu; Dan Yao; Yiming Wang; Guiqian Tang (Journal of Environmental Sciences, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Biogeomorphology and carbon sequestration in a coastal shoal invaded by Spartina alterniflora in the Yangtze Estuary: 22-year simulation for management implication - Ke-Hua Zhu; Zhen-Ming Ge; Ying Huang; Lei-Hua Zhao; Zeng-Feng Li; Wei Zhao; Hua-Yu Chen; Dan Zhang; Hai-Feng Cheng; Wei Zhang; Pei Xin (Ecological Engineering, 2025)

Intermittent energisation of microbial electrolysis cells enhances methanogenesis and reduces antibiotic resistance genes risk in sludge anaerobic digestion - Cheng Peng; Tianfeng Wang; Lu Jiang; Jie Wang; Jiazi Niu; Dan Luo; Liqing Xin; Wei Peng; Xia Zhao; Huixia Feng (Chemical Engineering Journal, 2025)

An in-situ multiresponsive flexible sensor utilizing electrochemical impedance spectroscopy for the precise and simultaneous detection of pressure, temperature, and humidity - Yin He; Shuang Xiao; Qi Wang; Cheng Guo; Dan Luo; Haibo Sun; Peng Zhou; Hao Liu (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Enhanced lignocellulose degradation and humification during the co-composting of cattle manure and tree branches: Synergism of microbial inoculation, biochar, and MnO2 - Wengao Shangguan; Muyuan Zhang; Shang Cheng; Dan Song; Yiyuan Wei; Mengjuan Wang; Xiaoxuan Su; Yuting Zhang; Ran Xiao (Process Safety and Environmental Protection, 2025)

Study of cable layout selection for oval cross-section submerged floating tunnel under wave-current coupling action - Chong Ji; Mengqi Tian; Xiantao Zhang; Xin Li; Ke Li; Dan Zhong; Liang Cheng; Hao Ding (Ocean Engineering, 2025)

Analysis of the influence of key structural parameters on the dynamic response of oval cross-section SFT under wave-current action - Hao Ding; Chong Ji; Mengqi Tian; Ke Li; Liang Cheng; Dan Zhong; Xiantao Zhang; Xin Li (Ocean Engineering, 2025)

Tracking crystal-melt segregation and accumulation in mushy reservoirs: Implication for silicic magma formation in tarim large igneous province - ChangQuan Li; Zhaochong Zhang; Changhong Wang; Zhiguo Cheng; Dan Gao (Lithos, 2025)

Enhanced heavy metal stability of sludge anaerobic digestion by different dosages of air nanobubble water - Tianfeng Wang; Ziying Xu; Jie Wang; Siqi Ren; Cheng Peng; Dan Luo; Xuemei Zhang; Miaozhi Yang (Journal of Water Process Engineering, 2025)

Photooxidation-pyrolysis coupling for sustainable management of photocured waste: Degradation of hazardous photoinitiators and resource recovery - Hongnan Zhang; Yunan Sun; Guandong Chen; Dan Zeng; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plant and its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Corrigendum to “Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one” [FLORA Volume 326, May 2025, 152724] - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

Dinotefuran exposure induces immunotoxicity in zebrafish embryos - Yunshuo Cheng; Yacan Gong; Dan Li; Weiwei Feng; Yao Chen; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Versatile defect-laden boronizing hard carbon for superior sodium-ion battery efficacy - Jiayi Wen; Cheng Liu; Mingjun Jing; Dan Li; Honghui Hu; Huaxin Liu; Tianjing Wu; Lanhua Yi; Yong Pei; Xue Zhong; Wentao Deng; Guoqiang Zou; et al. (Chemical Engineering Journal, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Two new cadinane-type sesquiterpene glycosides from Dendrobium findleyanum - Zi-Xi Lin; Zhong-Quan Cheng; Dan Yang (Natural Product Research, 2025)

Effect of humidity on hydrogen production reaction and explosion characteristics of aluminum powder: A comparative study between industrial polishing dust and spherical aluminum powder - Qi Jing; Zhiyuan Yang; Wanyun Cheng; Yuntao Li; Dan Wang (Process Safety and Environmental Protection, 2025)

Prediction of trihalomethane occurrence and cancer risk using interpretable machine learning and virtual data augmentation - Zhaopeng Li; Wencheng Ma; Yu Ouyang; Pengyuan Cheng; Dan Zhong (Journal of Hazardous Materials, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Experimental investigation and molecular simulations of CQDs for asphaltene deposition inhibition during CO2-EOR - Hang Ye; Qi Liu; Tong Wu; Wanzhen Xue; Chunkai Wang; Kai Cheng; Tiong Michelle; Dan Luo; Chenggang Xian; Yiqun Liu (Fuel, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

The multifaceted nature of SUMOylation in heart disease and its therapeutic potential - Ying He; Zhijie Yang; Dan Guo; Cheng Luo; Qiaoqiao Liu; Lei Xian; Fan Yang; Chusheng Huang; Qingjun Wei (Molecular and Cellular Biochemistry, 2025)

Influence of biochar on DOM formation in chicken manure composting: spectral properties and molecular weight analysis - Xiaolong Liu; Nennen Zhu; Ao Cheng; Xiujuan Zhou; Dan Chen; Ting Li; Xufang Yu; Wenchao Ji; Xingjun Fan (Environment, Development and Sustainability, 2025)

Evaluation of Seaweed Meal and Konjac Glucomannan Mixture as Feed Ingredients in Largemouth Bass Micropterus salmoides - Yan-Bo Cheng; Dan Wu; Liang Gao; Shun Rong; Guo-Huan Xu; Xu-Fang Liang (Fishes, 2025)
To address the negative effects of high-starch diets on largemouth bass (LMB), this study evaluated the feasibility of using a Gracilaria lemaneiformis-konjac glucomannan mixture (GKM, 2:1) as a substitute for strong flour (SF). Four iso-nitrogenous and iso-lipid diets were formulated: a control (15% SF; GK00) and three other diets replacing 33.3% (GK05), 66.7% (GK10), or 100% (GK15) of SF with GKM. Each diet was randomly administered to triplicate tanks of fish (10.49 ± 0.232 g) for a 10-week feeding trial. Results showed that the GKM inclusion groups significantly improved the fish survival and feed intake. Fish in GK05 and GK10 groups exhibited significantly higher final body weight, weight gain, and specific growth rate than the GK00 group, while GK15 showed no significant increase in these metrics. There was no impairment in protein, lipid, phosphorus, and energy retention efficiency in the GK05 and GK10 groups compared to those of the GK00 group. Apparent digestibility for feed dry matter, protein, lipid, phosphorus, and the 16 amino acids was not decreased in the GK05 and GK10 groups relative to the GK00 group. In addition, this study revealed reduced phosphorus waste per kilogram of weight gain in GK05 and GK10. In conclusion, these findings position GKM as a sustainable alternative to SF in feed for LMB.

Two new sesquiterpene glycosides from Dendrobium findleyanum - Zhongquan Cheng; Weiwei Fan; Jiangmiao Hu; Dan Yang (Natural Product Research, 2025)

Co-occurrence and integrated risk assessment of microplastics and antibiotic resistance genes in informal landfills: Evidence from Zhejiang Province, China - Lichen Liang; Houhu Zhang; Cheng Zhang; Lili Wang; Dan Wang; Yuanshun Xu (Process Safety and Environmental Protection, 2025)

Baoslingzhines Q−X: Structurally previously undescribed trace phenolic meroterpenoids from Ganoderma lucidum and their biological activities toward renal fibrosis and cytotoxicity - Yun-Yun Liu; Dan Cai; Xin-Ping Tang; Yong-Xian Cheng (Phytochemistry, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Lentiviral vectors for gene therapy of α-thalassemia - Saijuan Xu; Dan Liang; Yan Cheng; Gongrui Sun; Feiyan Zhao; Yang Yang; Haokun Zhang; Yongrong Lai; Bin Fu; Yuxuan Wu (Science China Life Sciences, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

MiR-3202–DTL signaling axis impedes NSCLC malignancy via regulating the ubiquitination-proteasome degradation of p21 - Hongjuan Guo; Qianbin Tang; Yujie Zhao; Jianghao Cheng; JunJie Wang; Dan Liu; Ruyu Yan; Dongjin Lv; Bingxiao Lu; Mingsong Wu; Hongtao Yu; Hao Leng; et al. (Molecular and Cellular Biochemistry, 2025)

Application of sourdough in gluten-free bakery products - Hangyan Dan; Hongyu Li; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Teng Hui; Wenjuan Wu; Zhen Zeng; Yuntao Liu (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Structural response analysis of different submerged floating tunnel route selection conditions in the complex strait under the action of typhoon Sepat - Cheng Cui; Bo Huang; Minglin Chen; Wenlong Luo; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Mechanistic impact of organics on electro-induced transformation of iron oxides and simultaneous uranium immobilization in wastewater - Mi Li; Dan Huang; Lanlan Cao; Sheng Liu; Xiaoyan Wu; Zhaowen Cheng; Xiaowen Zhang; Yilong Hua; Ying Peng; Qi Fang; Tao Cai (Journal of Hazardous Materials, 2025)

Diet dependent trophic transfer of nanoparticles (ZnO and TiO2) along the “photic biofilm-snail” food chain - Yu Cheng; Quanbo Yu; Weihua Zhang; Zhiqiang Liu; Jue Ding; Hongzhe Pan; Yiping Li; Dan Wu; Minghua Zhu; Xianchuan Xie; Ningyuan Zhu (Journal of Hazardous Materials, 2025)

Enhanced polylactic acid plastic biodegradation during aerobic composting of cattle manure and wheat straw by nanobubble water - Tianfeng Wang; Yuqian Zhang; Yu Zhang; Cheng Peng; Jianghe Chen; Yuxin Zhang; Ziying Xu; Dan Luo; Jining Zhang (Journal of Environmental Chemical Engineering, 2025)

Enhanced photocatalytic activity of nitrogen-carbon co-doped TiO2 for air pollution mitigation on cement-based surfaces - Dan Wang; Chunping Liu; Chen Yang; Junjie Li; Xin Cheng (Journal of Environmental Chemical Engineering, 2025)

Resource utilization of the waste lithium slag in oil-well cement under high temperature: Mechanical property, hydration behavior and environmental effect - Zhao Feng; Zeng Xueling; Long Dan; Gu Anlin; Mei Kaiyuan; Zhang Chunmei; Cheng Xiaowei (Journal of Environmental Chemical Engineering, 2025)

Co-hydrothermal carbonization of lignocellulosic biomass and swine manure for humic substance abundant target products: Impacts of hydrothermal temperature and feedstock composition - Weijie Xiong; Muyuan Zhang; Yiyuan Wei; Dan Song; Yuping Luo; Jiangtao Wang; Shang Cheng; Ran Xiao (Journal of Environmental Chemical Engineering, 2025)

Exploration of the structural features and anti-oxidative activity of whey protein hydrolysates produced by Lactiplantibacillus plantarum - Cuicui Duan; Shunan Hu; Cheng Wu; Yi Zhang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Battery-free antenna sticker for wireless sensing joint rotation - Pengxiang Si; Mingrui Liang; Jihua Zou; Yu Kuang; Juntao Zhang; Qingsha S. Cheng; Yiqian Kong; Yuxin Cai; Guozhi Huang; Yun Wu; Zhu Long; Boxin Zhao; et al. (Chemical Engineering Journal, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

A novel piperine derivative HJ-23 exhibits anti-colorectal cancer effects by activating the p53 pathway - Meiqi Zhang; Ruotong Liu; Wentao Jiang; Hanxue Li; Siyi Zhang; Wenhao Cheng; Xiaoqing Ye; Jingliang He; Yuanyuan Liu; Aixin Jing; Yizhuo Song; Dan Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Sterilization of Channel Catfish (Ictalurus punctatus) via Overexpression of bax Gene Regulated by a Tet-off System in the Primordial Germ Cells - Zhi Ye; Ahmed Elaswad; Guyu Qin; Dongdong Zhang; Baofeng Su; Karim Khalil; Zhenkui Qin; Nermeen Y. Abass; Qi Cheng; Ramjie Odin; Khoi Vo; Nathan Backenstose; et al. (Marine Biotechnology, 2025)

Provenance of Upper Jurassic in North Yellow Sea Basin, Eastern North China Craton - Haitian Yu; Zhongjie Xu; Rihui Cheng; Duo Wan; Dan Gao; Zhen Zhang (Journal of Earth Science, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Psychedelics for treating psychiatric disorders: from circuit mechanisms to applications - Jie Li; Yuting Jiang; Dan Cheng; Jianjun Cheng; Ji Hu; Xiaohui Wang; Ti-Fei Yuan (Science Bulletin, 2025)

Long-term response mechanism of bacterial communities to chemical oxidation remediation in petroleum hydrocarbon contaminated groundwater - Wenjuan Jia; Zhimao Deng; Marco Petrangeli Papini; Lirong Cheng; Naifu Jin; Dan Zhang; Zhengyan Li; Dayi Zhang; Yi Zhu; Aizhong Ding (Journal of Hazardous Materials, 2025)

Different benefit from clonal integration of stress signal between a stoloniferous alien invasive plantand its congeneric native one - Jie Deng; Jiao Tian; Cheng-Gang Qiu; Xue-Mei Wang; Jie Jiang; Han-Jun Yang; Yi Dan; Chang-Fan Chen; Su-Juan Duan; Jin-Song Chen (Flora, 2025)

A Novel Model of Traumatic Optic Neuropathy Under Direct Vision Through the Anterior Orbital Approach in Non-human Primates - Zhi-Qiang Xiao; Xiu Han; Xin Ren; Zeng-Qiang Wang; Si-Qi Chen; Qiao-Feng Zhu; Hai-Yang Cheng; Yin-Tian Li; Dan Liang; Xuan-Wei Liang; Ying Xu; Hui Yang (Neuroscience Bulletin, 2025)

MiR-214 inhibits NF-κB pathway activation to alleviate lipopolysaccharide-induced mastitis by targeting TRAF1 - Yujin Gao; Cheng Li; Xijun Zhang; Dan Yao; Yong Zhang (Theriogenology, 2025)

Convective injection into stratospheric intrusions alters the tropopause chemical structure - Zhixiong Chen; Jiajia Su; Jane Liu; Xiushu Qie; Valerie Thouret; Jianchun Bian; Dan Li; Zhixuan Bai; Xian Xiao; Xugeng Cheng; Mengmiao Yang; Lei Shu; et al. (Science Bulletin, 2025)

Pickering emulsion stabilized by egg derived reconstituted lipid nanoparticles for encapsulation and oral delivery of curcumin - Dan Han; Lihua Ji; Mingzhou Lu; Dingran Li; Xiangling Sheng; Jiaxing Zhang; Cheng Wang (Food Chemistry, 2025)

Dust storm detection for ground-based stations with imbalanced machine learning - Shikang Du; Siyu Chen; Shanling Cheng; Jiaqi He; Dan Zhao; Xusheng Zhu; Lulu Lian; Xingxing Tu; Qinghong Zhao; Yue Zhang (Environmental Modelling & Software, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Associations between environmental air pollution, greenspace and apparent biological aging: a cross-sectional study - Yijing Zhao; Xuena Yang; Dan He; Wenming Wei; Bolun Cheng; Feng Zhang (GeroScience, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Development of 3D printed zanthoxylum oil waxy rice cake - Zepeng Gu; Junlin Li; Qiyun Zhang; Hangyan Dan; Wenjuan Wu; Cheng Li; Zhengfeng Fang; Fahad Al-Asmari; Manal Y. Sameeh; Yuntao Liu; Zhen Zeng (Journal of Food Engineering, 2025)

An exploration on the structural characteristics and antioxidant activities of casein hydrolysates fermented by Lactiplantibacillus plantarum A56 and A157 - Cuicui Duan; Lingfang Zhang; Cheng Wu; Yi Zhang; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Functionalizing separator for dual application in liquid and solid-state lithium metal batteries: Achieving stable cycling from − 20 °C to 60 °C - Chen Cheng; Changyong Zhao; Shuiping Cai; Yingkang Tian; Rongjin Lin; Dan Luo; Xiaofei Yang; Xuejie Gao; Runcang Sun (Chemical Engineering Journal, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Potentially harmful effects of micro-/nanoplastics on humans as well as protective actions of dietary natural products - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Dan-Dan Zhou; Si-Yu Huang; Si-Xia Wu; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan (Trends in Food Science & Technology, 2025)

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Bombyx mori PAT4 gene inhibits BmNPV infection and replication through autophagy - Kaifang Jia; Jinyang Wang; Dan Jiang; Xiangrui Ding; Qiaoling Zhao; Dongxu Shen; Zhiyong Qiu; Xuelian Zhang; Cheng Lu; Heying Qian; Dingguo Xia (Journal of Invertebrate Pathology, 2025)

Green and rapid quantitative detection of selenium in selenium-enriched kefir grain based on Fourier transform infrared spectroscopy - Menghui Li; Dan Shi; Yifan Cheng; Qilei Dang; Wenhui Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Chemistry, 2025)

Effects of high-temperature stages on the physicochemical properties and oxidation products formation of rapeseed oil with carnosic acid - Ying-dan Zhu; Yue-ting Luan; Cheng-liang Chai; Ya-lin Xue; Zhang-qun Duan (Food Chemistry, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Implantable ultralow-threshold upconversion lens with self-adaptive photoprotection for intraocular infrared vision - Dong Wang; Chunrui Wang; Yunfeng Zhang; Wenfei Xun; Dan Chen; Qikuan Cheng; Lu Zhang; Yang Liu; Guigang Li; Suli Wu; Huamin Zhou; Yunming Wang (Chemical Engineering Journal, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Genetic estimation of fat traits in sheep and association of its NR1H4 gene polymorphisms with tail fat deposition - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yuan zhao; Yukun Zhang; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Exploring the impact mechanisms on different mechanized airing approaches during second round heap fermentation of sauce-flavor Baijiu: From physicochemical parameters, microbial diversity to volatile flavor compounds - Diqiang Wang; Cheng Wu; Jianfeng Hu; Feng Hu; Liping Liu; Heou Huang; Junlin Yang; Wenyu Zhao; Dan Xie; Jian Zhang; Anran Zhu (Food Research International, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Performance and regional applicability analysis of a building low-carbon heating system based on PV/T-GSHP - Yong Zhang; Yang Zhao; Chao Cheng; Heng Zhang; Dan Gao; Haiping Chen; Jizhen Liu (Energy and Buildings, 2025)

Novel Cu2O(SO4)@NiO nanocomposite as peroxymonosulfate activator for effective degradation of ciprofloxacin - Wenyao Zhang; Bo He; Jiangwei Shang; Xuelian He; Shuxian Tian; Yunqing Liu; Dan Feng; Mianwei Chen; Xiuwen Cheng (Chemical Engineering Journal, 2025)

Neutrophil-mediated cordycepin-based nanoparticles for targeted treatment of acute lung injury - Mengqi Gao; Huizhen Fan; Sifei Yu; Jun Huang; Decui Cheng; Lianfu Deng; Bing Zhao; Dan Xu; Min Lu; Enqiang Mao (Chemical Engineering Journal, 2025)

Aromatic Chinese medicine-decorated mesoporous nanoenzyme overcomes multiple biological barriers for solid tumor treatment - Xiaolong Quan; Ben Hu; Yibing Li; Iman Zare; Fengyong Cheng; Huiqi Huang; Jun Liu; Peng Cao; Dan Zhou; Meng Yu (Chemical Engineering Journal, 2025)

Peroxymonosulfate activation by ZnO-ZnMnO3/CuS nanocomposite for efficient degradation of ciprofloxacin based on a non-radical pathway: The promoting effect of CuS on electron transfer - Ming Yi; Jiangwei Shang; Shikai Zhang; Xinrui Gan; Chunjin Song; Shiyan Xu; Yunqing Liu; Dan Feng; Xiuwen Cheng (Chemical Engineering Journal, 2025)

Peroxymonosulfate activation by Ni–Co nanoparticles encapsulated in nitrogen-doped carbon derived from Co-doped Ni metal–organic frameworks for efficient enrofloxacin degradation - Shihu Cao; Yaqi Yin; Shugang Zheng; Chunjin Song; Xinrui Gan; Wenyao Zhang; Dan Feng; Jiangwei Shang; Xiuwen Cheng (Chemical Engineering Journal, 2025)

The high molecular weight and large particle size and high crystallinity of starch increase gelatinization temperature and retrogradation in glutinous rice - Cheng Liang; Yiman Han; Haoyang Xu; Dan Liu; Chunyan Jiang; Qingyu Li; Yungao Hu; Xunchao Xiang (Carbohydrate Polymers, 2025)

PLCFishMOT: multiple fish fry tracking utilizing particle filtering and attention mechanism - Huachao Tan; Yuan Cheng; Dan Liu; Guihong Yuan; Yanbo Jiang; Hongyong Gao; Hai Bi (Aquaculture International, 2025)

Generation of isotopically enriched giant Lincang Batholith by disequilibrium melting of the heterogeneous lower crust - Jin-Cheng Xie; Di-Cheng Zhu; Qing Wang; Peter A. Cawood; Zhi-Dan Zhao; Qiong-Yao Zhan; Jia-Hao Fan; Yao Wang (Lithos, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Metabolomics integrated with mass spectrometry imaging reveals novel action of tetramethylpyrazine in migraine - Ziwei Xing; Yu Chen; Junren Chen; Cheng Peng; Fu Peng; Dan Li (Food Chemistry, 2024)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

A study on the synergistic interaction of pea protein isolate and whey protein isolate for enhancing the stability and quality of krill oil emulsion - Danping Jin; Yuping Qu; Weibo Lu; Lijun Ge; Haifeng Wang; Jing Xue; Dan Deng; Qiong Zhang; Keyun Cheng; Huijuan Yang; Qing Shen (Food Hydrocolloids, 2024)

Enhancing microfiltration membrane performance by sodium percarbonate-based oxidation for hydraulic fracturing wastewater treatment - Haiqing Chang; Yingyuan Zhu; Naiming Liu; Pengwei Ji; Zhongsen Yan; Xiaoxiang Cheng; Dan Qu; Heng Liang; Fangshu Qu (Environmental Research, 2024)

Exposure to greenspaces sourced soils improves mice gut microbiota - Gang-Long Zhou; Yan Xie; Yi-Dan Zhang; Lu Wang; Yu-Ting Xie; Hui-Ling Qiu; Xiao-Qi Zhu; Jian-Cheng Jiang; Yan Yang; Mingdeng Xiang; Guang-Hui Dong; Yuanzhong Zhou; et al. (Environmental Pollution, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Paenibacillus lacisoli sp. nov., a mesotrione-degrading strain isolated from lakeside soil - Qimiao Xu; Bin Liu; Yingying Wan; Xueting Jiang; Le Chen; Dongmei Mao; Gang Chen; Dan Cheng; Jian He; Qirong Shen (Antonie van Leeuwenhoek, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

Ganospirones A−G, seven undescribed spiro-meroterpenoids from Ganoderma lucidum and their biological activities - Dan Li; Sheng-Hong Li; Qiang Gao; Qi Luo; Yong-Xian Cheng (Phytochemistry, 2024)

Seismic sedimentology analysis of meter-scale thin sand bodies in the Jurassic Qigu Formation, Yongjin area, Junggar Basin - Xin Hu; Xiaomin Zhu; Xuling Jin; Cheng Huang; Changling Cheng; Jinlei Xiu; Xincheng Ren; Dan Zheng (Marine and Petroleum Geology, 2024)

Optimal algae species inoculation strategy for algal-bacterial granular sludge: Sludge characteristics, performance and microbial community - Rui Cheng; Dan Huang; Xiaochen Xu; Fenglin Yang (Journal of Environmental Management, 2024)

Structural characteristics and gelling properties of citrus pectins after chemical and enzymatic modifications: Conformation plays a vital role in Ca2+-induced gelation - Jiefen Cui; Dan Liu; Yuyang Zhang; Mengyu Ma; Mengshan Shang; Cheng Zhao; Xingmiao Lu; Chengying Zhao; Jinkai Zheng (Food Chemistry, 2024)

Emulsions stabilized by okra polysaccharides: Physicochemical, interfacial, and emulsification properties - Yue Lv; Xiujuan Cai; Ting Xv; Hongxu Gao; Yuan Xv; Yuchao Gu; Dan Cheng; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2024)

Multiple-model based simulation of urban atmospheric methane concentration and the attributions to its seasonal variations: A case study in Hangzhou megacity, China - Junqing Zhang; Dan Ji; Cheng Hu; Timothy J. Griffis; Qitao Xiao; Xinyue Ai; Huili Liu; Xuejing Shi; Fan Sun; Bing Qi; Wei Xiao (Environmental Pollution, 2024)

The oxidative potential of fine ambient particulate matter in Xinxiang, North China: Pollution characteristics, source identification and regional transport - Huanjia Liu; Mengyuan Xu; Ying Yang; Ke Cheng; Yongli Liu; Yujuan Fan; Dan Yao; Di Tian; Lanqing Li; Xingzi Zhao; Ruiqin Zhang; Yadi Xu (Environmental Pollution, 2024)

Smart macrophage-targeting wound dressings accelerate diabetic wound healing - Junren Chen; Maozhu Luo; Yu Chen; Ziwei Xing; Cheng Peng; Dan Li (Chemical Engineering Journal, 2024)

Efficient degradation of Enrofloxacin with novel magnetic MnFe2O4/NiS2 composite as an activator of peroxymonosulfate - Dan Feng; Xiangchen Li; Shihu Cao; Shugang Zheng; Yaqi Yin; Chunjin Song; Yawen Gao; Nasen Bate; Jiangwei Shang; Xiuwen Cheng (Chemical Engineering Journal, 2024)

Migration of membrane fouling with minimal damage to cell integrity by catalytic ceramic membrane systems in low dosages of ozone during algae-laden water treatment - Dan Song; Xiaodie Han; Jiahui Li; Wei Cheng; Caihong Liu; Chuandong Wu; Jie Qiu; Jun Ma; Zhiqiang Sun (Chemical Engineering Journal, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Tourmaline triggered biofilm transformation: Boosting ultrafiltration efficiency and fouling resistance - Dan Song; Lu Wang; Weikai Sun; Yingjie Zhang; Binghan Xie; Ying Zhao; Wei Wang; Peizhi Wang; Jun Ma; Wei Cheng (Water Research, 2024)

Characteristics of pollutant generation from 3D-printed photocured waste combustion - Guanyi Chen; Yuru Song; Hongnan Zhang; Yunan Sun; Dan Zeng; Zhanjun Cheng; Beibei Yan (Waste Management, 2024)

Tuning d-band center of Pt via Pt-Pt5La heterostructure interface as efficient and stable electrocatalyst for oxygen reduction and methanol oxidation reactions in DMFCs - Ziqi Wan; Xinhao Wan; Jianqi Ye; Hao Su; Guanda Cheng; Jie Gao; Wei Gao; Dan Wen (Chemical Engineering Journal, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

Analysis of resting status reveals distinct elevational variation in metabolisms of lizards - Zhong‐Wen Jiang; Liang Ma; Shi‐ang Tao; Cheng Wenda; Chuyu Cheng; Dan‐yang Wu; Wei‐Guo Du (Ecology, 2024)
Animals spend a considerable proportion of their life span at rest. However, resting status has often been overlooked when investigating how species respond to environmental conditions. This may induce a large bias in understanding the local adaptation of species across environmental gradients and their vulnerability to potential environmental change. Here, we conducted an empirical study on montane agamid lizards, combined with mechanistic modeling, to compare elevational variations in body temperature and metabolisms (cumulative digestion and maintenance cost) between resting and active status. Our study on three populations of an agamid lizard along an elevational gradient revealed a trend of decreasing body temperature toward higher elevations, the main contributor of which was resting status of the lizards. Using population‐specific reaction norms, we predicted greater elevational variation in hourly and cumulative digestion for resting lizards than for active lizards. Climate‐change impacts, estimated as the change in cumulative digestion, also show greater elevational variation when resting status is factored into the analysis. Further, our global analysis of 98 agamid species revealed that in about half of their combined distributional range, the contribution of resting status in determining the elevational variation in cumulative digestion and maintenance cost of lizards was greater than the contribution made by a lizard's active status. Our study highlights the importance of considering resting status when investigating how species respond to environmental conditions, especially for those distributed over tropical and subtropical mountain areas.

Chemical constituents from the roots of Dolomiaea souliei - Zhe Wang; Li-Dan Zhang; Gang-Gang Zhou; Qi-Zheng Zhong; Yun-Bin Jiang; Guo-Wei Wang; Zhi-Hua Liao; Fan-Cheng Meng; Min Chen (Natural Product Research, 2024)

Real-time monitoring of maize phenology with the VI-RGS composite index using time-series UAV remote sensing images and meteorological data - Ziheng Feng; Zhida Cheng; Lipeng Ren; Bowei Liu; Chengjian Zhang; Dan Zhao; Heguang Sun; Haikuan Feng; Huiling Long; Bo Xu; Hao Yang; Xiaoyu Song; et al. (Computers and Electronics in Agriculture, 2024)

A method to rapidly construct 3D canopy scenes for maize and their spectral response evaluation - Dan Zhao; Tongyu Xu; Michael Henke; Hao Yang; Chengjian Zhang; Jinpeng Cheng; Guijun Yang (Computers and Electronics in Agriculture, 2024)

The value of pocket parks in preserving urban butterfly diversity - Shujing Zhang; Dan Han; Junying She; Qing Shen; Cheng Wang (Urban Forestry & Urban Greening, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Expression of ovine MYH3 gene and its polymorphisms and association analysis with growth traits in Hu sheep - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yukun Zhang; Yuan Zhao; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2024)

Prediction of DEDI index for meteorological drought with the VMD-CBiLSTM hybrid model - Tao Su; Dan Liu; Xingyuan Cui; Xianshen Dou; Bo Lei; Xu Cheng; Mengning Yuan; Renjie Chen (Journal of Hydrology, 2024)

Increased nitrogen accumulation in mulberry trees due to the secretion of glomalin-related soil protein induced by arbuscular mycorrhizal fungi - Huirong Zhang; Hongguang Cheng; Fang Zhang; Shiqing Peng; Yanjin Shi; Chaobin Luo; Xueping Tian; Zhenhong Wang; Dan Xing (European Journal of Soil Biology, 2024)

Data-driven approach for air pollutant concentrations forecasting: A window-based multi-output GBRT approach - Shikang Du; Siyu Chen; Shanling Cheng; Jiaqi He; Chuwei Liu; Lulu Lian; Chao Zhang; Dan Zhao; Nan Yin; Yawen Guan (Atmospheric Research, 2024)

Early senescence of pancreatic β cells induced by unfolded protein response deficiency prevents type 1 diabetes - Haipeng Cheng; Zhenwang Zhao; Dan Liu; Yufei Wang; Min Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

Rainfall Induced Slope Reliability Analysis Using Radial Degraded Random Fields - Chao Wang; Liang Li; Hailei Kou; Yungming Cheng; Dan Meng (Geotechnical and Geological Engineering, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Leaf area index estimation in maize and soybean using UAV LiDAR data - Shezhou Luo; Weiwei Liu; Qian Ren; Hanquan Wei; Cheng Wang; Xiaohuan Xi; Sheng Nie; Dong Li; Dan Ma; Guoqing Zhou (Precision Agriculture, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Investigating skeletal deformities in Murray cod (Maccullochella peelii): a comprehensive study combining transcriptomics and histology - Dan Song; Di Peng; Xinpeng Zhu; Qiqun Cheng (Aquaculture International, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Eliminating adverse effects of fouling layer using composite membranes with dense surface layers for sustainable membrane distillation of high-strength wastewater - Peizhi Wang; Jiawei Cheng; Jinxin Yao; Yuling Ma; Chuandong Wu; Dan Song; Wei Cheng; Jun Ma; Wei Wang (Desalination, 2024)

Decitabine-based nanoparticles for enhanced immunotherapy of hepatocellular carcinoma via DNA hypermethylation reversal - Hongqiao Cai; Xiaocheng Li; Yahui Liu; Jianji Ke; Kaiyu Liu; Yixin Xie; Cheng Xie; Dan Zhou; Mingda Han; Bai Ji (Chemical Engineering Journal, 2024)

Impact of model resolution and its representativeness consistency with observations on operational prediction of PM2.5 with 3D-VAR data assimilation - Ying Wei; Xiujuan Zhao; Ziyin Zhang; Jing Xu; Siyu Cheng; Zhiquan Liu; Wei Sun; Xueshun Chen; Zifa Wang; Xin Hao; Jiandong Li; Dan Chen (Atmospheric Pollution Research, 2024)

Retraction Note: Impact of Prenatal Acetaminophen Exposure for Hippocampal Development Disorder on Mice - Lulu Xie; Jiaxin Qin; Tingting Wang; Shuai Zhang; Mingcui Luo; Xuelei Cheng; Xinrui Cao; Hui Wang; Baozhen Yao; Dan Xu; Biwen Peng (Molecular Neurobiology, 2024)

Removal of canopy shadows improved retrieval accuracy of individual apple tree crowns LAI and chlorophyll content using UAV multispectral imagery and PROSAIL model - Chengjian Zhang; Zhibo Chen; Guijun Yang; Bo Xu; Haikuan Feng; Riqiang Chen; Ning Qi; Wenjie Zhang; Dan Zhao; Jinpeng Cheng; Hao Yang (Computers and Electronics in Agriculture, 2024)

Comparative analysis of the growth performance, vitality, body chemical composition and economic efficiency of the main cultivated strains of Pacific white shrimp (Litopenaeus vannamei) in coastal areas of China - Cheng Zhang; Chun-Yang Guo; Kai-He Shu; Shan-Liang Xu; Dan-Li Wang (Aquaculture, 2024)

Triphenyltin chloride exposure inhibits meiotic maturation of mouse oocytes by disrupting cytoskeleton assembly and cell cycle progression - Cong Ma; Hongzhen Ruan; Huiru Cheng; Zuying Xu; Caiyun Wu; Dan Liang; Huifen Xiang; Yunxia Cao; Zhiming Ding (Toxicology in Vitro, 2024)

Minor ergosteroids and a 19-nor labdane-type diterpenoid with anti-inflammatory effects from Ganoderma lucidum - Dan Cai; Yun-Yun Liu; Xin-Ping Tang; Mei Zhang; Yong-Xian Cheng (Phytochemistry, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Transport and retention of nanobubbles in saturated porous media: Overlooked role of grain size and shape - Dan Zhang; Wenke Wang; Yaqian Zhao; Minjuan Ma; Yan Cheng; Jianping Zhang; Ruyi Feng; Yan Zhao; Shengke Yang (Journal of Hydrology, 2024)

Nanobubble water promotes anaerobic digestion of high-solids cattle manure under mesophilic and thermophilic conditions - Qingfang Zhang; Ruoyu Wu; Ziying Xu; Yutong Feng; Cheng Peng; Hailong Shi; Yuqian Zhang; Linhai Yang; Dan Luo; Peng Dong; Wenqi Gao; Tianfeng Wang (Environmental Research, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Recognition of ethylene plasma image based on dual residual with attention mechanism network - Baoxia Li; Wenzhuo Chen; Shaohuang Bian; A Lusi; Xiaojiang Tang; Yang Liu; Junwei Guo; Dan Zhang; Cheng Yang; Feng Huang (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Influence of soil amendments on the growth and cadmium accumulation of rice in high-cadmium-contaminated agricultural soils: a pot experiment - Mengyuan Wang; Dan Wang; Liangzhe Yang; Yangyang Zhang; Wei Zhou; Jiali Yan; Hao Cheng (Cereal Research Communications, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Domestic hot-water boilers harbour active thermophilic bacterial communities distinctly different from those in the cold-water supply - Thomas Egli; Lena Campostrini; Mats Leifels; Hans Peter Füchslin; Claudia Kolm; Cheng Dan; Stefan Zimmermann; Vivian Hauss; Alexandre Guiller; Luigino Grasso; Adrian Shajkofci; Andreas H. Farnleitner; et al. (Water Research, 2024)

Analysis of the dynamic response of submerged floating tunnels to wave-induced loads, incorporating joint mechanical properties - Jie Hou; Bo Huang; Peng Chen; Hao Ding; Jianting Zhou; Ke Li; Liang Cheng; Qingyang Ren; Dan Zhong (Ocean Engineering, 2024)

Recent advances in environmental applications of Semi-coke: Energy storage, adsorption and catalysis - Xiangchen Li; Jiangwei Shang; Xinrui Gan; Shihu Cao; Tianning Zhang; Jing Nie; Dan Feng; Xiuwen Cheng (Journal of Environmental Chemical Engineering, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

CyHV-2 infection triggers mitochondrial-mediated apoptosis in GiCF cells by upregulating the pro-apoptotic gene ccBAX - Wenjie Cheng; Yilin Ren; Chenwei Yu; Tianqi Zhou; Ye Zhang; Liqun Lu; Yanli Liu; Dan Xu (Fish & Shellfish Immunology, 2024)

Circularly polarized room-temperature phosphorescence based on chiral co-assembled helical nanofiber from chiral co-assembled liquid crystal co-polymer - Chao Liu; Hang Li; Yihan Chen; Dan Xu; Yixiang Cheng (Chemical Engineering Journal, 2024)

Ship Shaft-Rate Electric Field Signal Denoising Method Based on VMD-MSS - Ye Wang; Dan Wang; Cheng Chi; Zhentao Yu; Jianwei Li; Lu Yu (Journal of Marine Science and Engineering, 2024)
The presence of complex electromagnetic noise in the ocean significantly impacts the accuracy of ship shaft-rate electric field signal detection, necessitating the development of an effective denoising method to enhance detection precision. Nevertheless, traditional denoising methods encounter issues like low frequency resolution, challenging threshold configuration, and mode mixing. This study introduces a method that integrates variational mode decomposition (VMD) with multi-window spectral subtraction (MSS). The intrinsic mode functions (IMFs) of noisy signals are extracted using VMD, and the noise components within different IMFs are identified. The spectral features of both signal and noise within different IMFs are leveraged to eliminate noise signals via MSS. Subsequently, the denoised components of IMFs are rearranged to derive the denoised ship shaft-rate electric field signals, achieving noise reduction across various frequency bands. Following validation using simulation signals and empirical data, the noise reduction efficacy of VMD-MSS surpasses that of alternative methods, demonstrating robust performance even at low signal-to-noise ratios. The marine electromagnetic noise is effectively suppressed in the empirical data, while preserving the characteristics of ship’s shaft-rate signals, thereby validating the method’s efficacy and demonstrating its practical engineering value.

Coupled dynamic analysis for wave action on a tension leg-type submerged floating tunnel in the frequency domain - Bo Huang; Wenlong Luo; Yue Chen; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2024)

Plasma pretreatment to enhance the sedimentation of ultrafine kaolinite particles: Experiments and mechanisms - Zhanglei Zhu; Bohui Zhao; Chengchi Tian; Yuan Zhang; Qiuyue Sheng; Mengyan Cheng; Ningning Zhang; Zhen Li; Dan Liu (Journal of Water Process Engineering, 2024)

Long-term ambient air pollution and the risk of musculoskeletal diseases: A prospective cohort study - Bolun Cheng; Chuyu Pan; Qingqing Cai; Li Liu; Shiqiang Cheng; Xuena Yang; Peilin Meng; Wenming Wei; Dan He; Huan Liu; Yumeng Jia; Yan Wen; et al. (Journal of Hazardous Materials, 2024)

Unveiling a novel mechanism for competitive advantage of ciprofloxacin-resistant bacteria in the environment through bacterial membrane vesicles - Zuye Fang; Xinlu Zhao; Ziyuan Zhang; Jiayi Wu; Jiliang Cheng; Dan Lei; Nan Li; Ruiguang Ge; Qing-Yu He; Xuesong Sun (Journal of Hazardous Materials, 2024)

Biosynthesis of Ag2Se nanoparticles as a broad-spectrum antimicrobial agent with excellent biocompatibility - Qian-Wen Ren; Yan Wang; Jun Qian; Xiao-Xue Zhang; Yuan-Yuan Cheng; Dan Yu; Lu Lu; Yan Wang; Xue He; Hong Mei; Chao Wu (Journal of Hazardous Materials, 2024)

Preparation and evaluation of liquorice (Glycyrrhiza uralensis) and ginger (Zingiber officinale) kombucha beverage based on antioxidant capacities, phenolic compounds and sensory qualities - Ruo-Gu Xiong; Dan-Dan Zhou; Jin Cheng; Si-Xia Wu; Adila Saimaiti; Si-Yu Huang; Qing Liu; Ao Shang; Hua-Bin Li; Sha Li (International Journal of Gastronomy and Food Science, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Molecular-level transformations of biomass burning-derived water-soluble organic carbon during dark aqueous OH oxidation: Insights from absorption, fluorescence, high-performance size exclusion chromatography and high-resolution mass spectrometry analysis - Xingjun Fan; Shuwen Xie; Xufang Yu; Ao Cheng; Dan Chen; Wenchao Ji; Xiaolong Liu; Jianzhong Song; Pingan Peng (Science of The Total Environment, 2024)

Enzymatically prepared neoagarooligosaccharides improve gut health and function through promoting the production of spermidine by Faecalibacterium in chickens - A La Teng Zhu La; Depeng Li; Zhiqian Cheng; Qiu Wen; Die Hu; Xiaolu Jin; Dan Liu; Yuqing Feng; Yuming Guo; Gong Cheng; Yongfei Hu (Science of The Total Environment, 2024)

Molecular and functional characterization of heat-shock protein 70 in Aphis gossypii under thermal and xenobiotic stresses - Pingzhuo Liang; Mingyu Guo; Dan Wang; Ting Li; Ren Li; Dapeng Li; Shenhang Cheng; Congai Zhen; Lei Zhang (Pesticide Biochemistry and Physiology, 2024)

Lava–water–sediment interaction: Dolomite U Pb dating marks the Cenozoic Ocean–continent transformation in the southwestern Tianshan Mountains - Dan Gao; Zhiguo Cheng; Zhaochong Zhang; Yoldash Osmani; Zhenchao Wang; Liangliang Zhang (Lithos, 2024)

The impact of urban polycentricity on carbon emissions: A case study of the Yangtze River Delta Region in China - Cheng Wang; Yunbin Zhang; Jingyuan Chen; Dan Li; Meng Zhu; Zhiqiang Gan (Journal of Cleaner Production, 2024)

Intermittent energization improves anaerobic digestion of microbial electrolysis cell-assisted nitrogen-rich sludge under mesophilic and thermophilic conditions - Qingfang Zhang; Cheng Peng; Jiajia Pu; Yutong Feng; Hong Zhu; Miaozhi Yang; Ziying Xu; Yuqian Zhang; Linhai Yang; Dan Luo; Tianfeng Wang (Journal of Environmental Chemical Engineering, 2024)

Boosted photothermal synergistic CO2 methanation over Ru doped Ni/ZrO2 catalyst: From experimental to DFT studies - Xin Ding; Xu Liu; Jiahui Cheng; Dan Li; Tengfei Li; Zhao Jiang; Yang Guo (Fuel, 2024)

Corrigendum to “Procyanidin B2: A promising multi-functional food-derived pigment for human diseases” [Food Chem. 420 (2023) 136101] - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2024)

Decoding the key compounds responsible for the empty cup aroma of soy sauce aroma type baijiu - Dan Qin; Silei Lv; Yi Shen; Jie Shi; Yingli Jiang; Wei Cheng; Dongmei Wang; Hehe Li; Yanyan Zhang; Huan Cheng; Xingqian Ye; Baoguo Sun (Food Chemistry, 2024)

STING signaling in islet macrophages impairs insulin secretion in obesity - Ze Hong; Saihua Chen; Jing Sun; Dan Cheng; Hanli Guo; Jiahao Mei; Xiang Zhang; Munire Maimaiti; Haiping Hao; Peng Cao; Haiyang Hu; Chen Wang (Science China Life Sciences, 2024)

MEIC-global-CO2: A new global CO2 emission inventory with highly-resolved source category and sub-country information - Ruochong Xu; Dan Tong; Qingyang Xiao; Xinying Qin; Cuihong Chen; Liu Yan; Jing Cheng; Can Cui; Hanwen Hu; Wenyu Liu; Xizhe Yan; Huaxuan Wang; et al. (Science China Earth Sciences, 2024)

Observation of a Bone Invasion Model of Aspergillus fumigatus In Vitro and Analysis of the Antifungal Susceptibility - Yan Shao; Min Shen; Dan Peng; Wenxu Cheng; Chenggang Mao; Heng Zhang; Yi Sun (Mycopathologia, 2024)

Sibship analysis revealed the reproductive strategy and current population status of the silver carp (Hypophthalmichthys molitrix) from the middle and lower reaches of the Yangtze River, China - Ping Yang; Cheng Chen; Dan Yu; Minzheng Li; Huanzhang Liu (Conservation Genetics, 2024)

Selenium-Enriched Cardamine violifolia Alleviates LPS-Induced Hepatic Damage and Inflammation by Suppressing TLR4/NODs–Necroptosis Signal Axes in Piglets - Dan Wang; Wenshuai Xie; Wensheng He; Huiling Zhu; Yue Zhang; Qingyu Gao; Xin Cong; Shuiyuan Cheng; Yulan Liu (Biological Trace Element Research, 2024)

Key issues to consider toward an efficient constructed wetland-microbial fuel cell: the idea and the reality - Diaodiao Li; Yaqian Zhao; Dan Wei; Cheng Tang; Ting Wei (Environmental Science and Pollution Research, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Enhanced azo dye reduction at semiconductor-microbe interface: The key role of semiconductor band structure - Hefei Shi; Xinbai Jiang; Xiaojiao Wen; Cheng Hou; Dan Chen; Yang Mu; Jinyou Shen (Water Research, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Vertical distribution of VOCs in the boundary layer of the Lhasa valley and its impact on ozone pollution - Dan Yao; Yinghong Wang; Zhixuan Bai; Mengtian Cheng; Guiqian Tang; Yuting Liu; Deqing Zhuoga; Hao Yu; Jianchun Bian; Yuesi Wang (Environmental Pollution, 2024)

A “toxic window” study on the hippocampal development of mice offspring exposed to azithromycin at different doses, courses, and time during pregnancy - Liyi Wei; Tingting Wang; Mingcui Luo; Shuai Zhang; Mengxi Lu; Xinli Zhou; Xuelei Cheng; Hui Wang; Dan Xu (Chemico-Biological Interactions, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

IL-4-secreting CD40L+ MAIT cells support antibody production in the peripheral blood of Heonch–Schönlein purpura patients - Muziying Liu; Ziqiang Yang; Qielan Wu; Yunru Yang; Dan Zhao; Qingyu Cheng; Yajuan Li; Gengyuan Liu; Changfeng Zhao; Jun Pan; Yuwei Zhang; Fang Deng; et al. (Inflammation Research, 2024)

Imaging peroxynitrite in endoplasmic reticulum stress and acute lung injury with a near-infrared fluorescent probe - Ke Yang; Ying Liu; Min Deng; Peipei Wang; Dan Cheng; Songjiao Li; Longwei He (Analytica Chimica Acta, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

CuCo2S4 microporous composite membrane to activate peroxymonosulfate for carbamazepine removal - Jiangwei Shang; Shuwen Fan; Shihu Cao; Xinrui Gan; Jing Nie; Tianning Zhang; Xiangchen Li; Dan Feng; Xiuwen Cheng (Journal of Environmental Chemical Engineering, 2023)

Ingenious use of autocatalytic hydrodeoxygenation for the separation and recovery of oil and iron from rolling oil sludge - Mingze An; Wangzhe Xia; Kai Cheng; Junjiang Zhu; Xianze Yin; Dan Luo; Jianhong Wu; Minggui Xia (Environmental Research, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

Spontaneous compartmentalization in chitosan - phytate - lignosulfonate microparticles by gas-shearing microfluidics - Qingli Qu; Long Chen; Weixia Cheng; Jules Muhire; Anquan Yang; Jing Wang; Min Xie; Xiaoli Zhang; Dan Huang; Ranhua Xiong; Dong Pei; Chaobo Huang (Chemical Engineering Journal, 2023)

PatU3 plays a central role in coordinating cell division and differentiation in pattern formation of filamentous cyanobacterium Nostoc sp. PCC 7120 - Lei Yin; Zhenggao Zheng; Yilin Li; Xiying Li; Dan Cheng; Chunxia Dong; Yixuan Liu; Jindong Zhao (Science China Life Sciences, 2023)

RETRACTED ARTICLE: Impact of Prenatal Acetaminophen Exposure for Hippocampal Development Disorder on Mice - Lulu Xie; Jiaxin Qin; Tingting Wang; Shuai Zhang; Mingcui Luo; Xuelei Cheng; Xinrui Cao; Hui Wang; Baozhen Yao; Dan Xu; Biwen Peng (Molecular Neurobiology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Two new cadinene-type sesquiterpene glycosides from Dendrobium findlayanum - Zhongquan Cheng; Weiwei Fan; Dan Yang; Jiangmiao Hu (Natural Product Research, 2023)

Carnosol analogue WK-63 alleviated cancer cachexia by inhibiting NF-κB and activating AKT pathways in muscle while inhibiting NF-κB and AMPK pathways in adipocyte - Xiaojuan Pan; Gang Zhang; Kun Wei; Xiaofan Gu; Jiahuan Dan; Yun Zhao; Xuan Liu; Chunru Cheng; Xiongwen Zhang (Toxicology and Applied Pharmacology, 2023)

Exposure to polycyclic aromatic hydrocarbons (PAHs) in outdoor air and respiratory health, inflammation and oxidative stress biomarkers: A panel study in healthy young adults - Huilin Zhang; Ranran Liu; Liu Yang; Hong Cheng; Shengchun Wang; Bin Zhang; Jiyuan Shao; Shengtao Ma; Dan Norbäck; Xin Zhang; Taicheng An (Science of The Total Environment, 2023)

Possible underestimation of the coal-fired power plants to air pollution in China - Zhixiong Weng; Yuqi Song; Cuiyun Cheng; Dan Tong; Meng Xu; Minghao Wang; Yang Xie (Resources, Conservation and Recycling, 2023)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Study on the relationship between primary structure/ spatial conformation and gel properties of pectins from different varieties - Jiefen Cui; Lin Zhang; Jirong Wang; Shaojie Zhao; Cheng Zhao; Dan Liu; Wenxiang Li; Jinkai Zheng (Food Hydrocolloids, 2023)

Public participation and outgoing audit of natural resources: Evidence from tripartite evolutionary game in China - Zhenhua Zhang; Dan Ling; Wenjia Tian; Cheng Zhou; Malin Song; Shuai Fang (Environmental Research, 2023)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

Investigating the molecular weight distribution of atmospheric water-soluble brown carbon using high-performance size exclusion chromatography coupled with diode array and fluorescence detectors - Xingjun Fan; Ao Cheng; Dan Chen; Tao Cao; Wenchao Ji; Jianzhong Song; Pingan Peng (Chemosphere, 2023)

Geochemical relationship and profile distribution of Selenium and Cadmium in typical Selenium-enriched areas in Enshi - Chengfeng Jiang; Wei Zhou; Liangzhe Yang; Jiali Yan; Shuxin Tu; Yuan Yuan; Dan Wang; Hao Cheng (Chemosphere, 2023)

Expression of aldose reductase in mouse endometrial epithelial cells and its role in sperm capacitation - Yi Lei; Li Nie; Yun Long; Dan Zhao; Min Liu; Yi-cheng Wang; Xue-qin Zhang; Miao-miao Xu; Huan Liu; Jin-hu Zhang; Dong-zhi Yuan; Li-min Yue (Theriogenology, 2023)

Anti-inflammatory polyoxygenated cyclohexene derivatives from Uvaria macclurei - Yexin Cheng; Hailong Li; Dan Wu; Yayue Hu; Jinhe Li; Ying Yang; Jiahang Li; Honggang Zhou; Hongfeng Zhang; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

City-level environmental performance and the spatial structure of China's three coastal city clusters - Dan Wu; Yuying Lie; Li Liu; Ziye Cheng; Yujie Zhang; Yuxiang Yang; Wenjun Xiao; Suli Li; Guangyang Luo; Zhen Wang (Journal of Cleaner Production, 2023)

Comprehensive overview of antibiotic distribution, risk and priority: A study of large-scale drinking water sources from the lower Yangtze River - Ning Wang; Na Wang; Dan Qi; Guodong Kang; Wei Wang; Cheng Zhang; Zhenhua Zhang; Yan Zhang; Houhu Zhang; Shenghu Zhang; Jingjing Xu (Journal of Environmental Management, 2023)

Late Mesozoic transformation from the compressive to extensional tectonic regime of the Eastern North China Craton: Sedimentary records from the North Yellow Sea Basin - Haitian Yu; Zhongjie Xu; Rihui Cheng; Zhen Zhang; Dan Gao (Journal of Asian Earth Sciences, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Extremely stable deep-blue organic light-emitting diodes employing diindolophenazine-based fluorophore with narrow-band emission and a shallow LUMO level - Cong Cheng; Yunhui Zhu; Taiju Tsuboi; Chao Deng; Weiwei Lou; Tiangeng Liu; Dan Wang; Qisheng Zhang (Chemical Engineering Journal, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

The Mitochondrial-Derived Peptide (MOTS-c) Interacted with Nrf2 to Defend the Antioxidant System to Protect Dopaminergic Neurons Against Rotenone Exposure - Jingsong Xiao; Qifu Zhang; Yaohui Shan; Feng Ye; Xi Zhang; Jin Cheng; Xiaogang Wang; Yuanpeng Zhao; Guorong Dan; Mingliang Chen; Yan Sai (Molecular Neurobiology, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

Cadmium accumulation in rice grains is mitigated by duckweed-like hydrophyte through adsorption and increased ammonia nitrogen - Shaoning Chen; Junhui Xu; Liang Peng; Ziyi Cheng; Xiaolin Kuang; Dan Li; Cheng Peng; Huijuan Song (Science of The Total Environment, 2023)

Optimal design of a glider array for the observation of tropical cyclones - Yutong Sun; Dan Cheng; Shaoqiong Yang; Chenyi Luo; Di Tian; Han Zhang; Yanhui Wang (Progress in Oceanography, 2023)

Projection of drought-flood abrupt alternation in a humid subtropical region under changing climate - Rong Wang; Xianghu Li; Qi Zhang; Junxiang Cheng; Jianfeng Li; Dan Zhang; Yuanbo Liu (Journal of Hydrology, 2023)

Fertilizer-induced manganese oxide formation enhances cadmium removal by paddy crusts from irrigation water - Xiaolin Kuang; Liang Peng; Ziyi Cheng; Siyan Zhou; Shaoning Chen; Cheng Peng; Huijuan Song; Changwu Li; Dan Li (Journal of Hazardous Materials, 2023)

Association between rice protein components and eating quality traits of different rice varieties under different nitrogen levels - Lina Li; Shijie Shi; Bo Cheng; Dan Zhao; Keqiang Pan; Cougui Cao; Yang Jiang (Journal of Cereal Science, 2023)

Procyanidin B2: A promising multi-functional food-derived pigment for human diseases - Junren Chen; Kexin Zhong; Yiqi Jing; Shengmeng Liu; Siqi Qin; Fu Peng; Dan Li; Cheng Peng (Food Chemistry, 2023)

Carbendazim exposure inhibits mouse oocytes meiotic maturation in vitro by destroying spindle assembly - Cong Ma; Zhuonan Yang; Shouxin Zhang; Xueke Zhang; Siyuan Wang; Huiru Cheng; Yang Liu; Hongzhen Ruan; Zuying Xu; Chunmei Liang; Dan Liang; Zhiming Ding; et al. (Food and Chemical Toxicology, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Endowing V6O13/CeVO4 heterojunction with substantial improvements on zinc ion storage performance - Jingyun Cheng; Shuai Nan; Shuang Yu; Kaitao Liu; Huaiqiang Gu; Lei Tan; Zhulin Niu; Dan Li; Hongqiang Wang (Chemical Engineering Journal, 2023)

Bone targeting miR-26a loaded exosome-mimetics for bone regeneration therapy by activating Wnt signaling pathway - Liuzhi Hao; Shuwen Huang; Tongling Huang; Dan Yi; Chenmin Wang; Lixin Cheng; Min Guan; Jun Wu; Di Chen; Haobo Pan; William W. Lu; Xiaoli Zhao (Chemical Engineering Journal, 2023)

HSP90/CDC37 inactivation promotes degradation of LKB1 protein to suppress AMPK signaling in bronchial epithelial cells exposed to sulfur mustard analog, 2-chloroethyl ethyl sulfide - Feng Ye; Xiaogang Wang; Haoyin Liu; Xunhu Dong; Jin Cheng; Mingliang Chen; Guorong Dan; Yan Sai; Zhongmin Zou (Chemico-Biological Interactions, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Selenium-enriched Cardamine violifolia protects against sepsis-induced intestinal injury by regulating mitochondrial fusion in weaned pigs - Dan Wang; Yanling Kuang; Qingqing Lv; Wenshuai Xie; Xiao Xu; Huiling Zhu; Yue Zhang; Xin Cong; Shuiyuan Cheng; Yulan Liu (Science China Life Sciences, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Climate change mitigation potential of kitchen waste utilization in China for combined heat and power production - Weiguo Liu; Dan Zhang; Jiajing Tian; Feiyan Yu; Yuanming Xie; Shengkui Cheng; Qiang Li; Weizhong Li; Changhui Peng; Yan Yan (Science of The Total Environment, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Experimental study on the decomposition and odor-release process of a decayed submerged plant—A case study of Potamogeton crispus - Dan Zhang; Xiaolong Cheng; Ran Li; Jingjie Feng; Lei Tang (Journal of Water Process Engineering, 2023)

Water-solubility croconic acid-bisindole dye with morpholine ring for tumor NIRF/PA imaging and photothermal therapy activated by lysosome pH-response - Pei-Dan You; Cheng-Ren Ouyang; Fei Lu; Chao Zeng; Hong-Die Cai; Guo-Sheng Shi; Lihong Liu; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

The potential of different ripeness of blood oranges (Citrus sinensis L. Osbeck) for sale in advance after low-temperature storage: Anthocyanin enhancements, volatile compounds, and taste attributes - Jin Chen; Yanru Zhang; Feifei Liu; Jianle Chen; Wenjun Wang; Dan Wu; Xingqian Ye; Donghong Liu; Huan Cheng (Food Chemistry, 2023)

Electrospinning technology on one dimensional microwave absorbers: fundamentals, current progress, and perspectives - Lixin Li; Zirun Chen; Fei Pan; Hongtao Guo; Xiao Wang; Jie Cheng; Lei Cai; Zheng Xiu; Linfeng Chen; Dan Batalu; Wei Lu (Chemical Engineering Journal, 2023)

Observation of nitrogen oxide-influenced chlorine chemistry and source analysis of Cl2 in the Yangtze River Delta, China - Fangbing Li; Dan Dan Huang; Wei Nie; Yee Jun Tham; Shengrong Lou; Yuanyuan Li; Linhui Tian; Yuliang Liu; Min Zhou; Haichao Wang; Liping Qiao; Hongli Wang; et al. (Atmospheric Environment, 2023)

Spatiotemporal variations and driving factors of global terrestrial vegetation productivity gap under the changing of climate, CO2, landcover and N deposition - Dan Cao; Jiahua Zhang; Tian Zhang; Fengmei Yao; Renxin Ji; Shuanjin Zi; Hong Li; QuanYing Cheng (Science of The Total Environment, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Review of characteristics, generation pathways and detection methods of singlet oxygen generated in advanced oxidation processes (AOPs) - Zhi-Hui Xie; Chuan-Shu He; Dan-Ni Pei; Yudan Dong; Shu-Run Yang; Zhaokun Xiong; Peng Zhou; Zhi-Cheng Pan; Gang Yao; Bo Lai (Chemical Engineering Journal, 2023)

Efficient mechanical exfoliation of MXene nanosheets - Yuchen Liu; Qi Tang; Mao Xu; Jie Ren; Chan Guo; Cheng Chen; Wenjing Geng; Weiwei Lei; Xiaoli Zhao; Dan Liu (Chemical Engineering Journal, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

miR ‐124 mediates the expression of ccBax to regulate Cyprinid herpesvirus 2 ( CyHV ‐2)‐induced apoptosis and viral replication - Yan Fu; Junzhe Zhang; Wenjie Cheng; Xingyu Cheng; Liqun Lu; Lang Gui; Yousheng Jiang; Ye Zhang; Dan Xu (Journal of Fish Diseases, 2023)
Cyprinid herpesvirus 2 (CyHV‐2), the etiological agent of herpesvirus haematopoietic necrosis (HVHN) in carp and goldfish, has caused significant economic losses in the aquaculture industry. During viral infection, the host initiates a series of active or passive defences to regulate the process of virus infection. Apoptosis is a key component of active cellular defence, and members of the Bcl‐2 family have been shown to play a critical role in the apoptotic process. However, the mechanism of action of the Bcl‐2 family in inducing apoptosis during CyHV‐2 infection remains unclear. In this study, we revealed the molecular mechanism of miRNA‐mediated silver crucian carp BAX (ccBax) in CyHV‐2‐induced apoptosis for the first time and demonstrated that the overexpression of miR‐124 suppressed ccBax expression and significantly down‐regulated apoptosis in caudal fin cells of Carassius auratus gibelio (GiCF), while miR‐124 inhibitors were the opposite. These studies indicated that miR‐124 inhibits CyHV‐2‐induced apoptosis by reducing the expression of ccBax. Furthermore, the fact that transfection of miR‐124 mimics promoted CyHV‐2 replication, whereas miR‐124 inhibitors inhibited CyHV‐2 replication, indicated that miR‐124 inhibited CyHV‐2‐induced apoptosis and contributed to viral replication. All these results suggested that miR‐124 suppresses virus‐induced apoptosis and promotes viral replication by targeting and regulating ccBax expression.

Long‐term variability in the fish assemblage around Japan over the last century and early warning signals of regime shifts - Yongjun Tian; Caihong Fu; Akihiko Yatsu; Yoshiro Watanabe; Yang Liu; Jianchao Li; Dan Liu; Yumeng Pang; Jiahua Cheng; Ching‐Hsein Ho; Shuyang Ma (Fish and Fisheries, 2023)
The marine ecosystems around Japan are very productive and have typical wasp‐waist structure dominated by small pelagic fishes such as sardine, exhibiting large low‐frequency fluctuations in biomass. Whereas studies on the variability in abundance of individual species such as sardine and anchovy are popular, only a few studies focused on the long‐term variability of fish assemblage around Japan. In this study, 13 species/taxa ranging from small forage to large predatory species and from warm‐ to cold‐water species were selected to indicate essential characteristics of the fish assemblage and their drivers were analysed based on fishery, oceanographic and climatic data sets from 1901 to 2018. Results show that two outstanding peaks during the 1930s and 1980s were characterized by abundant sardine. Additionally, species composition showed high similarities during similar temperature regimes while exhibiting contrasts during different temperature regimes. Variations and regime shifts in dominant patterns and fish community indices coincided well with the Atlantic Multidecadal Oscillation (AMO) and regional sea surface temperature (SST). Furthermore, gradient forest analysis identified AMO and regional SSTs as most important predictors of dominant patterns and fish community indices, suggesting that the decadal and multidecadal variability in the fish assemblage around Japan was forced by basin‐scale climate variability as inherent in the AMO through its connections with regional SSTs. Autocorrelation coefficient demonstrated that the ecological indicators have the potential to be early warning signals of regime shifts, which suggests the possibility of coming cold regime since around 2015 and has important implications for fisheries management.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Efficient degradation of micropollutants in CoCaAl-LDO/peracetic acid (PAA) system: An organic radical dominant degradation process - Zhi-Hui Xie; Chuan-Shu He; Dan-Ni Pei; Yun-Zhe Zheng; Xiao-Yu Wu; Zhaokun Xiong; Ye Du; Zhi-Cheng Pan; Gang Yao; Bo Lai (Journal of Hazardous Materials, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Bioactive compounds and health benefits of pomegranate: An updated narrative review - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Yibin Feng; Ren-You Gan; Hua-Bin Li (Food Bioscience, 2023)

Field test of Model Predictive Control in residential buildings for utility cost savings - Dan Wang; Yangzhe Chen; Wei Wang; Cheng Gao; Zhe Wang (Energy and Buildings, 2023)

Design of hybrid g-C3N4/GO/MCE photocatalytic membranes with enhanced separation performance under visible-light irradiation - Junyang Pan; Dan Hua; Yiping Hong; Xi Cheng; Fangsong Guo; Kok Bing Tan; Ziqi Zhong; Guowu Zhan (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

ARPC5 is transcriptionally activated by KLF4, and promotes cell migration and invasion in prostate cancer via up-regulating ADAM17 - GenYi Qu; YuLong Zhang; HongTao Duan; Cheng Tang; Guang Yang; Dan Chen; Yong Xu (Apoptosis, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Expression profiles of the CD274 and PLEKHH2 gene and association of its polymorphism with hematologic parameters in sheep - Yukun Zhang; Xiaoxue Zhang; Fadi Li; Changchun Lin; Deyin Zhang; Benzhen Duan; Yuan Zhao; Xiaolong Li; Dan Xu; Jiangbo Cheng; Liming Zhao; Jianghui Wang; et al. (Veterinary Immunology and Immunopathology, 2023)

A unique suit of Wuchiapingian marine red beds in central China representing a specific paleogeography and paleoclimate association - Cheng Cheng; Zi'an Shan; Mingyu Shan; Zhonglai Zhou; Bingyan Ren; Yike Chu; Shuangying Li; Dan Wang; Hongzuo Wang; Xujie Shu; Peng Qian (Marine and Petroleum Geology, 2023)

Optimization of a phase change material enhanced low-concentration photovoltaic/thermal module - Yang Zhao; Yu Huang; Na Wang; Yong Zhang; Chao Cheng; Heng Zhang; Dan Gao (Energy and Buildings, 2023)

High-strength and recyclable pure chitosan films manufactured by an ionic liquid assisted roll-forming method - Shuang Sun; Jiaqi Zheng; Zijie Liu; Siluo Huang; Qikuan Cheng; Yue Fu; Weihao Cai; Dan Chen; Dong Wang; Huamin Zhou; Yunming Wang (Chemical Engineering Journal, 2023)

Phosphorus transformation behavior and phosphorus cycling genes expression in food waste composting with hydroxyapatite enhanced by phosphate-solubilizing bacteria - Shaoqi Xu; Kaixue Jia; Yi Zheng; Wenjie Chen; Zhigang Wang; Dan Wei; Baoru Sun; Meidi Cheng; Beibei Fan; Ji Li; Yuquan Wei (Bioresource Technology, 2023)

Graphite oxide as an electronic conductor modified ZIF-8/NH2-MIL-125(Ti) hybrid material used as a photocatalyst for removal of organic dyes under visible light irradiation - Yuhao Liu; Jieqi Wang; Xuyi Wang; Jiayue Chen; Beibo Zhang; Liping Chen; Dan Zheng; Ming Cheng (Environmental Science and Pollution Research, 2023)

Development of a Golgi-targeted superoxide anion fluorescent probe for elucidating protein GOLPH3 function in myocardial ischemia-reperfusion injury - Ao Li; Yalan Liu; Labapuchi; Zhe Chen; Songjiao Li; Rongbin Zhong; Dan Cheng; Linxi Chen; Longwei He (Analytica Chimica Acta, 2023)

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Elucidating pollution characteristics, temporal variation and source origins of carbonaceous species in Xinxiang, a heavily polluted city in North China - Huanjia Liu; Mengke Jia; Jie Tao; Dan Yao; Juexiu Li; Ruiqin Zhang; Lanqing Li; Mengyuan Xu; Yujuan Fan; Yongli Liu; Ke Cheng (Atmospheric Environment, 2023)

Construction of HClO activated near-infrared fluorescent probe for imaging hepatocellular carcinoma - Songjiao Li; Peipei Wang; Ke Yang; Ying Liu; Dan Cheng; Longwei He (Analytica Chimica Acta, 2023)

Facile construction of Z-scheme AgCl/Bi3TaO7 photocatalysts for effective removal of tetracycline under visible-light irradiation - Xiaoxin Guo; Jun Liu; Dan Li; Hongjun Cheng; Kankan Liu; Xiaoqing Liu; Tiansheng Liu (Environmental Science and Pollution Research, 2023)

One-pot synthesis of novel flower-like LaCO3OH adsorbents for efficient scavenging of phosphate from wastewater - Fulong Cheng; Fangui Nie; Yuting Fan; Dan Huang; Yinian Wang; Jianxin Fan (Environmental Science and Pollution Research, 2023)

Visible light enhanced persulfate activation for degradation of tetracycline via boosting adsorption of persulfate by ligand-deficient MIL-101(Fe) icosahedron - Gangya Cheng; Chen Yuan; Wansheng Ruan; Ben Ma; Xinyu Zhang; Xinjing Yuan; Zhihui Li; Dan Wang; Fei Teng (Chemosphere, 2023)

The structure-function relationships of pectins separated from three citrus parts: Flavedo, albedo, and pomace - Lin Zhang; Jiefen Cui; Shaojie Zhao; Dan Liu; Cheng Zhao; Jinkai Zheng (Food Hydrocolloids, 2023)

Commensal Bacillus siamensis LF4 induces antimicrobial peptides expression via TLRs and NLRs signaling pathways in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Cheng-Ye Wei; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Reinforcement learning control strategy for differential pressure setpoint in large-scale multi-source looped district cooling system - Dan Wang; Cheng Gao; Yuying Sun; Wei Wang; Shihao Zhu (Energy and Buildings, 2023)

Overexpressing SIRT6 can Attenuate the Injury of Intracerebral Hemorrhage by Down-Regulating NF-kB - Jing Cheng; Yan-Qin Fan; Wen-Fei Zhang; Guo Zhang; Kuo Zeng; Zhang Ye; Dan Zhao; Li-Quan Wu; Zhi-Biao Chen (NeuroMolecular Medicine, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Further undescribed cembranoids from South China Sea soft coral Sarcophyton ehrenbergi: Structural elucidation and biological evaluation - Meng-Jun Wu; Dan-Dan Yu; Ye-Qing Du; Juan Zhang; Ming-Zhi Su; Cheng-Shi Jiang; Yue-Wei Guo (Phytochemistry, 2023)

Zinc glycerolate (Glyzinc): A novel foliar fertilizer for zinc biofortification and cadmium reduction in wheat (Triticum aestivum L.) - Jiapan Lian; Liping Cheng; Xu Zhai; Ruofan Wu; Xiwei Huang; Dan Chen; Jianqing Pan; M.J.I. Shohag; Xiaoping Xin; Xinwei Ren; Zhenli He; Xiaoe Yang (Food Chemistry, 2023)

Defective engineering and heteroatom doping construction in carbon nanobowls for achieving high-rate potassium-ion storage with long cyclic life - Jinbao Wang; Yanchao Qin; Longhui Li; Shuo Zhang; Xiangdong Pei; Zhulin Niu; Xiu-Cheng Zheng; Dan Li (Chemical Engineering Journal, 2023)

Dopamine induced multiple bonding in hyaluronic acid network to construct particle-free conductive hydrogel for reliable electro-biosensing - Ming-Ze Zeng; Dan Wei; Jie Ding; Yuan Tian; Xiao-Yang Wu; Zhi-Hong Chen; Cheng-Heng Wu; Jing Sun; Hua-Bing Yin; Hong-Song Fan (Carbohydrate Polymers, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Comprehensive analysis of the combined flocculation and filtration process for microalgae harvesting at various operating parameters - Bingcong Zhang; Cheng Peng; Shuangshuang Zhang; Miao Zhang; Dan Li; Xin Wang; Bifei Mao (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

Multifunctional elastic rGO hybrid aerogels for microwave absorption, infrared stealth and heat insulation - Yuanjing Cheng; Xianxian Sun; Shuang Yang; Dan Wang; Lei Liang; Shasha Wang; Yuanhao Ning; Weilong Yin; Yibin Li (Chemical Engineering Journal, 2023)

Combining Bone Collagen Matrix with hUC-MSCs for Application to Alveolar Process Cleft in a Rabbit Model - Xue-Cheng Sun; Hu Wang; Dan Zhang; Jian-Hui Li; Li-Qiang Yin; Yu-Fang Yan; Xu Ma; Hong-Fei Xia (Stem Cell Reviews and Reports, 2023)

Dynamic mechanical characteristics of frozen subgrade soil subjected to freeze-thaw cycles - Dan Wang; En-long Liu; Cheng-song Yang; You-qian Liu; Sheng-xian Zhu; Qi-hao Yu (Journal of Mountain Science, 2023)

A mitochondrial-targeted near-infrared fluorescent probe for visualizing the fluctuation of hypochlorite acid in idiopathic pulmonary fibrosis mice - Songjiao Li; Peipei Wang; Ying Liu; Ke Yang; Rongbin Zhong; Dan Cheng; Longwei He (Analytica Chimica Acta, 2023)

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

Insight into the evolution characteristics on molecular weight of compost dissolved organic matters using high-performance size exclusion chromatography combined with a two-dimensional correlation analysis - Xufang Yu; Ao Cheng; Dan Chen; Ting Li; Xingjun Fan; Xiang Wang; Wenchao Ji; Jianfei Wang; Lantian Ren (Environmental Science and Pollution Research, 2022)

Recent Development of Algal Biochar for Contaminant Remediation and Energy Application: A State-of-the Art Review - Thanh-Binh Nguyen; Van-Truc Nguyen; Hong-Giang Hoang; Ngoc-Dan-Thanh Cao; Thanh-Tin Nguyen; Thi-Dieu-Hien Vo; Ngoc-Kim-Qui Nguyen; Mai-Duy-Thong Pham; Duc-Long Nghiem; Thi-Kim-Quyen Vo; Cheng-Di Dong; Xuan-Thanh Bui (Current Pollution Reports, 2022)

The transition from Palaeo-Asian to marginal Pacific tectonic domain experienced in the Eastern North China Craton: evidence from Late Jurassic sediment provenance in the North Yellow Sea Basin - Haitian Yu; Zhongjie Xu; Rihui Cheng; Duo Wan; Dan Gao; Zhen Zhang (Earth Science Informatics, 2022)

Glycoproteomic analysis reveals the effects of bisecting GlcNAc in intrahepatic cholangiocarcinoma - Wei Dan; Cheng Li; Jun Li; Pengfei Li; Miaomiao Xin; Zexuan Chen; Liuyi Dang; Zihao Yu; Jing Li; Jiechen Shen; Liangshuo Hu; Shisheng Sun (Glycoconjugate Journal, 2022)

An improved algae-YOLO model based on deep learning for object detection of ocean microalgae considering aquacultural lightweight deployment - Dan Liu; Pengqi Wang; Yuan Cheng; Hai Bi (Frontiers in Marine Science, 2022)
Algae are widely distributed and have a considerable impact on water quality. Harmful algae can degrade water quality and be detrimental to aquaculture, while beneficial algae are widely used. The accuracy and speed of existing intelligent algae detection methods are available, but the size of parameters of models is large, the equipment requirements are high, the deployment costs are high, and there is still little research on lightweight detection methods in the area of algae detection. In this paper, we propose an improved Algae-YOLO object detection approach, which is based on ShuffleNetV2 as the YOLO backbone network to reduce the parameter space, adapting the ECA attention mechanism to improve detection accuracy, and redesigning the neck structure replacing the neck structure with ghost convolution module for reducing the size of parameters, finally the method achieved the comparable accuracy. Experiments showed that the Algal-YOLO approach in this paper reduces the size of parameters by 82.3%, and the computation (FLOPs) is decreased from 16G to 2.9G with less loss of accuracy, and mAP by only 0.007 when compared to the original YOLOv5s. With high accuracy, the smaller model size are achieved, which reduces the equipment cost during actual deployment and helps to promote the practical application of algae detection.

Occurrence and distribution of antibiotics in coastal water of the Taizhou Bay, China: impacts of industrial activities and marine aquaculture - Ning Wang; Weitao Shen; ShengHu Zhang; Jie Cheng; Dan Qi; Jing Hua; Guodong Kang; Hui Qiu (Environmental Science and Pollution Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Fine mapping of the reduced height gene Rht22 in tetraploid wheat landrace Jianyangailanmai (Triticum turgidum L.) - Chao Wang; Yunjing Bao; Qin Yao; Dan Long; Xue Xiao; Xing Fan; Houyang Kang; Jian Zeng; Lina Sha; Haiqin Zhang; Dandan Wu; Yonghong Zhou; et al. (Theoretical and Applied Genetics, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Relationship between the spatial sampling intervals of high-density acquisition techniques and vertical resolution - Dan Jin; Jianyuan Cheng; Baoli Wang; Xuqian Dou; Qingqing Zhang (Arabian Journal of Geosciences, 2022)

Phosphorus removal by aquatic vegetation in shallow eutrophic lakes: a laboratory study - Dan Wu; Chunqi Shen; Yu Cheng; Jue Ding; Wei Li (Environmental Science and Pollution Research, 2022)

Rhizobium quercicola sp. nov., isolated from the leaf of Quercus variablis in China - Cheng-Bin Wang; Dan-Ran Bian; Ning Jiang; Han Xue; Chun-Gen Piao; Yong Li (Archives of Microbiology, 2022)

Clonidine ameliorates cerebral ischemia–reperfusion injury by up-regulating the GluN3 subunits of NMDA receptor - Jing Chen; Juan Zhang; Dan-Dan Yang; Zi-Cheng Li; Bo Zhao; Yue Chen; Zhi He (Metabolic Brain Disease, 2022)

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

Hb New York, preliminary results concerning the hematologic characteristics and the effects on thalassemia - Zhuru Cheng; Xiaonian Zhu; Dan Zeng; Qiao Feng; Baodong Tian; Haiqing Zheng; Shengkui Tan; Chunjiang Zhu (Molecular Biology Reports, 2022)

The tetrameric assembly of 2‐aminomuconic 6‐semialdehyde dehydrogenase is a functional requirement of cofactor NAD + binding - Qiuli Shi; Yanjuan Chen; Xinxin Li; Hui Dong; Cheng Chen; Zhihui Zhong; Cheng Yang; Guangfeng Liu; Dan Su (Environmental Microbiology, 2022)
Summary The bacterium Pseudomonas sp. AP‐3 is able to use the environmental pollutant 2‐aminophenol as its sole source of carbon, nitrogen, and energy. Eight genes (amnA, B, C, D, E, F, G, and H) encoding 2‐aminophenol metabolizing enzymes are clustered into a single operon. 2‐Aminomuconic 6‐semialdehyde dehydrogenase (AmnC), a member of the aldehyde dehydrogenase (ALDH) superfamily, is responsible for oxidizing 2‐aminomuconic 6‐semialdehyde to 2‐aminomuconate. In contrast to many other members of the ALDH superfamily, the structural basis of the catalytic activity of AmnC remains elusive. Here, we present the crystal structure of AmnC, which displays a homotetrameric quaternary assembly that is directly involved in its enzymatic activity. The tetrameric state of AmnC in solution was also presented using small‐angle X‐ray scattering. The tetramerization of AmnC is mediated by the assembly of a protruding hydrophobic beta‐strand motif and residues V121 and S123 located in the NAD + ‐binding domain of each subunit. Dimeric mutants of AmnC dramatically lose NAD + binding affinity and failed to oxidize the substrate analogue 2‐hydroxymuconate‐6‐semialdehyde to α‐hydroxymuconic acid, indicating that tetrameric assembly of AmnC is functional requirement.

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Prenatal Isoflurane Exposure Induces Developmental Neurotoxicity in Rats: the Role of Gut Microbiota - Li-Kuan Wang; Xu-Dong Yang; Dan Zhou; Tong Cheng; Xiang Zhang; Hai-Yin Wu (Neurotoxicity Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Melatonin secretion, molecular expression and evolution of MT1/2 in two Lasiopodomys species - Hong Sun; Dan Pan; Denghui Liu; Yuyang Cheng; Yifeng Zhang; Zhenlong Wang (Mammalian Biology, 2022)

Evolution of research topics on the Tibetan Plateau environment and ecology from 2000 to 2020: a paper mining - Keke Chang; Junyu Tao; Cheng Fang; Jian Li; Wenwu Zhou; Xutong Wang; Beibei Yan; Dan Zeng; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

A superpixel region merging based nonuniformity correction method for hyperspectral images - Xiaoyu Cheng; Zhouyin Cai; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Correction to: Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

Toward a phylogeny and biogeography of Diaphanosoma (Crustacea: Cladocera) - Henri J. Dumont; Bo-Ping Han; Fei Fei Guo; Hua Chen; Dan Cheng; Ping Liu; Lei Xu; La-Orsri Sanoamuang; Arnola C. Rietzler; Shaolin Xu; Andy Vierstraete; Manuel Elias-Gutierrez (Aquatic Ecology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

TLR2 Potentiates SR-Marco-Mediated Neuroinflammation by Interacting with the SRCR Domain - Lu Wang; Han-Yu Yang; Cai-Xia Zang; Jun-Mei Shang; Hui Liu; Zi-Hong Zhang; Fang-Yu Yuan; Cheng Ju; Fang-Yuan Li; Xiu-Qi Bao; Dan Zhang (Molecular Neurobiology, 2021)

PGC-1ɑ Mediated-EXOG, a Specific Repair Enzyme for Mitochondrial DNA, Plays an Essential Role in the Rotenone-Induced Neurotoxicity of PC12 Cells - Jingsong Xiao; Xunhu Dong; Kaige Peng; Feng Ye; Jin Cheng; Guorong Dan; Zhongmin Zou; Jia Cao; Yan Sai (Journal of Molecular Neuroscience, 2021)

Divergence in the Aquilegia ecalcarata complex is correlated with geography and climate oscillations: Evidence from plastid genome data - Cheng Xue; Fang‐Dong Geng; Jiao‐Jie Li; Dan‐Qing Zhang; Fei Gao; Lei Huang; Xiao‐Hui Zhang; Ju‐Qing Kang; Jian‐Qiang Zhang; Yi Ren (Molecular Ecology, 2021)
Quaternary climate oscillations and geographical heterogeneity play important roles in determining species and genetic diversity distribution patterns, but how these factors affect the migration and differentiation of East Asian plants species at the population level remains poorly understood. The Aquilegia ecalcarata complex, a group that originated in the Late Tertiary and is widely distributed throughout East Asia, displays high genetic variation that is suitable for studying elaborate phylogeographic patterns and demographic history related to the impact of Quaternary climate and geography. We used plastid genome data from 322 individuals in 60 populations of the A . ecalcarata complex to thoroughly explore the impact of Quaternary climate oscillations and geography on the phylogeographic patterns and demographic history of the A . ecalcarata complex through a series of phylogenetic, divergence time estimation, and demographic history analyses. The dry, cold climate and frequent climate oscillations that occurred during the early Pleistocene and the Mid‐Pleistocene transition led to the differentiation of the A . ecalcarata complex, which was isolated in various areas. Geographically, the A . ecalcarata complex can be divided into Eastern and Western Clades and five subclades, which conform to the divergence of the East Asian flora. Our results clearly show the impact of Quaternary climate and geography on evolutionary history at the population level. These findings promote the understanding of the relationship between plant genetic differentiation and climate and geographical factors of East Asia at the population level.

Gelidibacter maritimus sp. nov., isolated from marine sediment - Cheng Gao; He-Yuan Lun; Dan-Dan Shang; Min Cai; Meng-Qi Ye; Zong-Jun Du (Archives of Microbiology, 2021)

Pesticides Exposure and Dopaminergic Neurodegeneration - Jingsong Xiao; Xunhu Dong; Xi Zhang; Feng Ye; Jin Cheng; Guorong Dan; Yuanpeng Zhao; Zhongmin Zou; Jia Cao; Yan Sai (Exposure and Health, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Advantage of Multi-Directional Stability of Spiral Clavicle Plate in Treatment of Middle One-Third Clavicle Fracture: A Finite Element Study - Dan-Kai Wu; Wen-Chuan Chen; Kun-Jhih Lin; Cheng-Lun Tsai; Kang-Ping Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2021)

Gelidibacter pelagius sp. nov., Isolated from Coastal Sediment - He-Yuan Lun; Cheng Gao; Dan-Dan Shang; Ya Gong; Zong-Jun Du (Current Microbiology, 2021)

Natural constituents from food sources as therapeutic agents for obesity and metabolic diseases targeting adipose tissue inflammation - Dan Li; Tian Zhang; Jinjian Lu; Cheng Peng; Ligen Lin (Critical Reviews in Food Science and Nutrition, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

A spatial-spectral clustering-based algorithm for endmember extraction and hyperspectral unmixing - Xiaoyu Cheng; Zhouyin Cai; Jia Li; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Decline of SARS-CoV-2-specific IgG, IgM and IgA in convalescent COVID-19 patients within 100 days after hospital discharge - Huan Ma; Dan Zhao; Weihong Zeng; Yunru Yang; Xiaowen Hu; Peigen Zhou; Jianping Weng; Linzhao Cheng; Xueying Zheng; Tengchuan Jin (Science China Life Sciences, 2021)

Long Non-coding RNA MALAT1 Upregulates ZEB2 Expression to Promote Malignant Progression of Glioma by Attenuating miR-124 - Hongyu Cheng; Haikang Zhao; Xin Xiao; Qian Huang; Wen Zeng; Bo Tian; Tao Ma; Dan Lu; Yulong Jin; Yuqian Li (Molecular Neurobiology, 2021)

The metabolic and immunological characteristics of pregnant women with COVID-19 and their neonates - Jingjiao Zhou; Yudie Wang; Juan Zhao; Lixing Gu; Cheng Yang; Jun Wang; Heng Zhang; Yu Tian; Hu Tuo; Dan Li; Min Wei; Bing He (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2021)

Effects of Porphyromonas gingivalis and Its Underlying Mechanisms on Alzheimer-Like Tau Hyperphosphorylation in Sprague-Dawley Rats - Zhiqun Tang; Dan Liang; Miaoying Cheng; Xinyi Su; Runhe Liu; Yiding Zhang; Hongkun Wu (Journal of Molecular Neuroscience, 2021)

Land-use changes and ecosystem services under different scenarios in Nansi Lake Basin, China - Yande Jing; Yuqing Chang; Xiyu Cheng; Dan Wang (Environmental Monitoring and Assessment, 2021)

Clinical characteristics and plasma antibody titer of patients with COVID-19 in Zhejiang, China - Wei-ling Xiang; Jing-jing Cheng; Lian-peng Wu; Bing-yu Chen; Wen-xin Li; Dan-ying Qiu; Wei Zhang; Fei-hang Ge; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2020)

The spillover effects of China’s regional environmental markets to local listed firms: a risk Granger causality approach - Shujin Zhu; Yiding Tang; Xingzhi Qiao; Cheng Peng; Dan Li (Environmental Science and Pollution Research, 2020)

Arbuscular mycorrhizal fungal species identity governs plant water content and soil aggregation improvements under wet-dry climate conditions - Yan Wang; Dan Xing; Chao Bin Luo; Fang Zhang; Cheng Ming Zhang (Environmental Science and Pollution Research, 2020)

2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Yi-Feng Li; Xin Zhu; Zhi-Yang Cheng; Xiao Liang; You-Ting Zhu; Dan-Dan Feng; Sergey Dobretsov; Jin-Long Yang (Frontiers in Marine Science, 2020)

Sesquiterpene lactones from Artemisia austroyunnanensis suppresses ROS production and reduces cytokines, iNOS and COX-2 levels via NF-KB pathway in vitro - Lan Liu; Dan Liu; Cheng Xiang; Weifeng Dai; Baocai Li; Mi Zhang (Natural Product Research, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

RIG-I aggravates interstitial fibrosis via c-Myc-mediated fibroblast activation in UUO mice - Zhuanli Zhou; Jiayun Ni; Jingyao Li; Chuanbing Huo; Naijun Miao; Fan Yin; Qian Cheng; Dan Xu; Hongyan Xie; Panpan Chen; Peiqing Zheng; Yingying Zhang; et al. (Journal of Molecular Medicine, 2020)
Progressive tubulointerstitial fibrosis is the common final outcome for all kidney diseases evolving into chronic kidney disease (CKD), whereas molecular mechanisms driving fibrogenesis remain elusive. Retinoic acid-inducible gene-I (RIG-I), an intracellular pattern recognition receptor, is originally identified participating in immune response by recognizing virus RNA. Here, we revealed for the first time that RIG-I was induced in unilateral ureteral obstruction (UUO) and folic acid (FA) renal fibrosis models and moderate-degree renal fibrosis patients. Besides, we found RIG-I was mainly located in renal tubular epithelial cells and promoted the production and release of inflammatory cytokines, such as interleukin (IL)-1β and IL-6 through activation of NF-κB. Inflammatory cytokines released by tubular epithelial cells activated c-Myc-mediated TGF-β/Smad signaling in fibroblasts, which in turn aggravated interstitial fibrosis by promoting fibroblast activation and production of extracellular matrix components (ECM). Deficiency of RIG-I attenuated renal fibrosis by the regulation of inflammatory responses, c-Myc expression, and fibroblast activation. Besides, gene silencing of RIG-I reduced inflammatory cytokines in cultured tubular epithelial cells treated with Angiotensin II. Knockdown of c-Myc or c-Myc inhibitor blocked IL-1β-induced fibroblast activation. Collectively, our study demonstrates that RIG-I plays a significant role in the progress of renal fibrosis via regulating c-Myc-mediated fibroblast activation. Key messages • RIG-I was constantly elevated in kidneys from renal fibrotic mice. • RIG-I facilitated inflammatory cytokine production in tubular epithelial cells. • RIG-I aggravated renal fibrosis via c-Myc-mediated TGF-β/Smad activation.

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Relationships amongst sex ratio of progeny in Anastatus disparis (Hymenoptera: Eupelmidae), sperm depletion and decreased fecundity - Peng-Cheng Liu; Hai-Xiang Wei; Dan-Dan Cao; Jian-Rong Wei (Applied Entomology and Zoology, 2020)

The root endophytic fungus Serendipita indica improves resistance of Banana to Fusarium oxysporum f. sp. cubense tropical race 4 - Chunzhen Cheng; Dan Li; Quan Qi; Xueli Sun; Mensah Raphael Anue; Bodjrenou Mahoudjro David; Yongyan Zhang; Xiangyang Hao; Zihao Zhang; Zhongxiong Lai (European Journal of Plant Pathology, 2020)

BMA probability quantitative precipitation forecasting of land-falling typhoons in south-east China - Linna Zhao; Xuemei Bai; Dan Qi; Cheng Xing (Frontiers of Earth Science, 2019)

Cyclin-dependent Kinase 18 Promotes Oligodendrocyte Precursor Cell Differentiation through Activating the Extracellular Signal-Regulated Kinase Signaling Pathway - Yuchen Pan; Zeping Jiang; Dingya Sun; Zhenghao Li; Yingyan Pu; Dan Wang; Aijun Huang; Cheng He; Li Cao (Neuroscience Bulletin, 2019)

Remote Sensing Image Matching Based Improved ORB in NSCT Domain - Dan Ma; Hui-cheng Lai (Journal of the Indian Society of Remote Sensing, 2019)

A dynamic Bayesian network-based model for evaluating rainfall-induced landslides - Wen Nie; Dan Feng; Worapong Lohpaisankrit; Cheng Li; Ji Yuan; Yulong Chen (Bulletin of Engineering Geology and the Environment, 2019)

Approach to the Geopolitical Influences of Great Powers in Southeast Asia: Case Studies of China and the US - Qi Qin; Shengkui Cheng; Fei Li; Shuwen Zhang; Liang Wu; Dan Zhang (Chinese Geographical Science, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

The Gibberellic Acid-Stimulated Transcript Gene Family in Moso Bamboo: A Genome-Wide Survey and Expression Profiling During Development and Abiotic Stresses - Dan Hou; Qingsong Bai; Juan Li; Lihua Xie; Xiangyu Li; Zhanchao Cheng; Jian Gao (Journal of Plant Growth Regulation, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Histological and cytological studies of plant infection by Erysiphe euonymi-japonici - Juanni Yao; Dan Yu; Yulin Cheng; Zhensheng Kang (Protoplasma, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Identification of a major QTL affecting resistance to brown spot in tobacco (Nicotiana tabacum L.) via linkage and association mapping methods - Mingming Sun; Lirui Cheng; Caihong Jiang; Chengguang Zhu; Min Ren; Yusheng Zhang; Yu Zhang; Dan Liu; Qiang Zhao; Ruimei Geng; Xiaoli Hu; Aiguo Yang; et al. (Euphytica, 2018)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Arsenic removal from water by metal-organic framework MIL-88A microrods - Hao Wu; Meng-Dan Ma; Wei-Zhuo Gai; Hongxun Yang; Jian-Ge Zhou; Zhenxiang Cheng; Pingguang Xu; Zhen-Yan Deng (Environmental Science and Pollution Research, 2018)

Telmisartan attenuates hydrogen peroxide-induced apoptosis in differentiated PC12 cells - Guan Tao Du; Xuan Ke; Guo Liang Meng; Guang Jun Liu; Hui Ying Wu; Jin Hong Gong; Xiao Dan Qian; Jin Luo Cheng; Hao Hong (Metabolic Brain Disease, 2018)

Rebirth after death: forest succession dynamics in response to climate change on Gongga Mountain, Southwest China - Gen-wei Cheng; Xu-yang Lu; Xiao-dan Wang; Jian Sun (Journal of Mountain Science, 2018)

Risk prediction in infective endocarditis by modified MELD-XI score - Peng-cheng He; Xue-biao Wei; Si-ni Luo; Xiao-lan Chen; Zu-hui Ke; Dan-qing Yu; Ji-yan Chen; Yuan-hui Liu; Ning Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Vitamin A-coupled liposomes carrying TLR4-silencing shRNA induce apoptosis of pancreatic stellate cells and resolution of pancreatic fibrosis - Yuwei Zhang; Dan Yue; Liuliu Cheng; Anliang Huang; Nanwei Tong; Ping Cheng (Journal of Molecular Medicine, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Myt1L Promotes Differentiation of Oligodendrocyte Precursor Cells and is Necessary for Remyelination After Lysolecithin-Induced Demyelination - Yanqing Shi; Qi Shao; Zhenghao Li; Ginez A. Gonzalez; Fengfeng Lu; Dan Wang; Yingyan Pu; Aijun Huang; Chao Zhao; Cheng He; Li Cao (Neuroscience Bulletin, 2018)

Weathered and Volcanic Provenance-Sedimentary System and Its Influence on Reservoir Quality in the East of the Eastern Depression, the North Yellow Sea Basin - Dan Gao; Rihui Cheng; Yanjie Shen; Liaoliang Wang; Xiaoqiang Hu (Journal of Earth Science, 2018)

N-Propargyl Caffeamide (PACA) Ameliorates Dopaminergic Neuronal Loss and Motor Dysfunctions in MPTP Mouse Model of Parkinson’s Disease and in MPP+-Induced Neurons via Promoting the Conversion of proNGF to NGF - Dan Luo; Jia Zhao; Yuanyuan Cheng; Simon Ming-Yuen Lee; Jianhui Rong (Molecular Neurobiology, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Complexity measurement of precipitation series in urban areas based on particle swarm optimized multiscale entropy - Dong Liu; Chen Cheng; Qiang Fu; Yongjia Zhang; Yuxiang Hu; Dan Zhao; Muhammad Imran Khan; Muhammad Abrar Faiz (Arabian Journal of Geosciences, 2018)

A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

MiR-30a Positively Regulates the Inflammatory Response of Microglia in Experimental Autoimmune Encephalomyelitis - Xue Fang; Dingya Sun; Zhihong Wang; Zhongwang Yu; Weili Liu; Yingyan Pu; Dan Wang; Aijun Huang; Mingdong Liu; Zhenghua Xiang; Cheng He; Li Cao (Neuroscience Bulletin, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Spatial and temporal expression of Sox9 during murine incisor development - Zhi-cheng Yang; Dan Li; Shuang Feng; Xiao-Dong Sui; Zhi Chen; Li Zhang (Journal of Molecular Histology, 2017)

Association of Toll-like receptor 3 gene polymorphism with the severity of enterovirus 71 infection in Chinese children - Hongfang He; Shihai Liu; Pei-pei Liu; Qiu-bo Li; Yu-xia Tan; Ya Guo; Fei Li; Yuan-yuan Wang; Ye-dan Liu; Cheng-qing Yang; Zong-bo Chen (Archives of Virology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Four new glycosides from the stems of Dendrobium fimbriatum Hook - Feng-Qing Xu; Wei-Wei Fan; Cheng-Ting Zi; Fa-Wu Dong; Dan Yang; Jun Zhou; Jiang-Miao Hu (Natural Product Research, 2017)

Prestack density inversion using the Fatti equation constrained by the P- and S-wave impedance and density - Li-Feng Liang; Hong-Bing Zhang; Zhi-Wei Dan; Zi-Qiang Xu; Xiu-Juan Liu; Cheng-Hao Cao (Applied Geophysics, 2017)

Genome-Wide Discovery of DNA Polymorphisms in Mei (Prunus mume Sieb. et Zucc.), an Ornamental Woody Plant, with Contrasting Tree Architecture and their Functional Relevance for Weeping Trait - Jie Zhang; Kai Zhao; Dan Hou; Junhuo Cai; Qixiang Zhang; Tangren Cheng; Huitang Pan; Weiru Yang (Plant Molecular Biology Reporter, 2017)

Occurrence, spatial distribution, and ecological risks of typical hydroxylated polybrominated diphenyl ethers in surface sediments from a large freshwater lake of China - Dan Liu; Sheng-min Wu; Qin Zhang; Min Guo; Jie Cheng; Sheng-hu Zhang; Cheng Yao; Jian-qiu Chen (Environmental Science and Pollution Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Overexpression of a heading Chinese cabbage ICE1 gene confers freezing tolerance in transgenic rice - Dianjun Xiang; Yongshan Chai; Lili Man; Yuyou Sun; Taizhong Zhang; Caiqiang Wei; Zhong Xie; Hongliang Li; Weiwei Zhang; Dan Liu; Dujuan Cheng; Xiaodong Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

The induction of apoptosis in SGC-7901 cells through the ROS-mediated mitochondrial dysfunction pathway by a Ir(III) complex - Cheng Zhang; Shang-Hai Lai; Chuan-Chuan Zeng; Bing Tang; Dan Wan; De-Gang Xing; Yun-Jun Liu (JBIC Journal of Biological Inorganic Chemistry, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Chemokines and their receptors in lung cancer progression and metastasis - Zeng-hui Cheng; Yu-xin Shi; Min Yuan; Dan Xiong; Jiang-hua Zheng; Zhi-yong Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Levels and distribution of organochlorine pesticides and hexachlorobutadiene in soils and terrestrial organisms from a former pesticide-producing area in Southwest China - Zhenwu Tang; Qifei Huang; Zhiqiang Nie; Yufei Yang; Jun Yang; Dan Qu; Jiali Cheng (Stochastic Environmental Research and Risk Assessment, 2016)

Dynamics of land use change in a mining area: a case study of Nadowli District, Ghana - Laari Prosper Basommi; Qing-feng Guan; Dan-dan Cheng; Sudhir Kumar Singh (Journal of Mountain Science, 2016)

Experimental Investigation on Non-Darcian Flow in Unbound Graded Aggregate Material of Highway Pavement - Han-Cheng Dan; Lin-Hua He; Bo Xu (Transport in Porous Media, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Erratum to: Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Polychlorinated dibenzo-p-dioxins, dibenzofurans, and dioxin-like polychlorinated biphenyls in sediments from the Yellow and Yangtze Rivers, China - Lirong Gao; Huiting Huang; Lidan Liu; Cheng Li; Xin Zhou; Dan Xia (Environmental Science and Pollution Research, 2015)

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Clinical and molecular genetic analysis of a Chinese family with congenital X-linked adrenal hypoplasia caused by novel mutation 1268delA in the DAX-1 gene - Zhe Zhang; Ye Feng; Dan Ye; Cheng-jiang Li; Feng-qin Dong; Ying Tong (Journal of Zhejiang University-SCIENCE B, 2015)

Wild soybean roots depend on specific transcription factors and oxidation reduction related genesin response to alkaline stress - Huizi DuanMu; Yang Wang; Xi Bai; Shufei Cheng; Michael K. Deyholos; Gane Ka-Shu Wong; Dan Li; Dan Zhu; Ran Li; Yang Yu; Lei Cao; Chao Chen; et al. (Functional & Integrative Genomics, 2015)

Effects of pre-harvest chemical application on rice desiccation and seed quality - Yong-qi He; Jin-ping Cheng; Liang-feng Liu; Xiao-dan Li; Bin Yang; Hong-sheng Zhang; Zhou-fei Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Genetic architecture of biofortification traits in soybean (Glycine max L. Merr.) revealed through association analysis and linkage mapping - Lihua Ning; Pingdong Sun; Qing Wang; Deyuan Ma; Zhenbin Hu; Dan Zhang; Guozheng Zhang; Hao Cheng; Deyue Yu (Euphytica, 2015)

Recent Advances in Methods and Techniques for Freshness Quality Determination and Evaluation of Fish and Fish Fillets: A Review - Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

Establishment of a picloram-induced somatic embryogenesis system in Vitis vinifera cv. chardonnay and genetic transformation of a stilbene synthase gene from wild-growing Vitis species - Lingmin Dai; Qi Zhou; Ruimin Li; Yangjian Du; Jing He; Dan Wang; Siyan Cheng; Jianxia Zhang; Yuejin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

A Comprehensive Transcriptome Provides Candidate Genes for Sex Determination/Differentiation and SSR/SNP Markers in Yellow Catfish - Xin Chen; Jie Mei; Junjie Wu; Jing Jing; Wenge Ma; Jin Zhang; Cheng Dan; Weimin Wang; Jian-Fang Gui (Marine Biotechnology, 2015)

Clinical Implications of BMI-1 in Cancer Stem Cells of Laryngeal Carcinoma - Dan Yu; Yan Liu; Jingpu Yang; Chunshun Jin; Xue Zhao; Jinzhang Cheng; Xueshibojie Liu; Xinmeng Qi (Cell Biochemistry and Biophysics, 2015)

Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2015)

Effects of short-term conservation management practices on soil organic carbon fractions and microbial community composition under a rice-wheat rotation system - Li-Jin Guo; Zhi-Sheng Zhang; Dan-Dan Wang; Cheng-Fang Li; Cou-Gui Cao (Biology and Fertility of Soils, 2015)

Erratum to: Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2014)

Monitoring of urban heat island in Shanghai, China, from 1981 to 2010 with satellite data - Cheng-fan Li; Di Shen; Jiang-shan Dong; Jing-yuan Yin; Jun-juan Zhao; Dan Xue (Arabian Journal of Geosciences, 2014)

Use of single nucleotide polymorphisms and haplotypes to identify genomic regions associated with protein content and water-soluble protein content in soybean - Dan Zhang; Guizhen Kan; Zhenbin Hu; Hao Cheng; Yu Zhang; Qing Wang; Hui Wang; Yuming Yang; Hongyan Li; Derong Hao; Deyue Yu (Theoretical and Applied Genetics, 2014)

Diffusion Source Detection of Volcanic Ash Cloud Using MODIS Satellite Data - Cheng-Fan Li; Yang-Yang Dai; Jun-Juan Zhao; Jing-Yuan Yin; Dan Xue; Shi-Qiang Zhou (Journal of the Indian Society of Remote Sensing, 2014)

One-step synthesis of bentonite-supported nanoscale Fe/Ni bimetals for rapid degradation of methyl orange in water - Dan Zhao; Jing Cheng; Jiawei Chen (Environmental Chemistry Letters, 2014)

Triiodothyronine regulates distribution of thyroid hormone receptors by activating AMP-activated protein kinase in 3T3-L1 adipocytes and induces uncoupling protein-1 expression - Cheng-Zhi Wang; Dan Wei; Mei-Ping Guan; Yao-Ming Xue (Molecular and Cellular Biochemistry, 2014)

Rickettsia raoultii, the predominant Rickettsia found in Dermacentor silvarum ticks in China–Russia border areas - Jing Wen; Dan Jiao; Jian-hua Wang; De-hai Yao; Zhi-xiang Liu; Gang Zhao; Wen-dong Ju; Cheng Cheng; Yi-jing Li; Yi Sun (Experimental and Applied Acarology, 2014)

Application of RNA interference methodology to investigate and develop SCMV resistance in maize - DEFANG GAN; FEI DING; DAN ZHUANG; HAIYANG JIANG; TONG JIANG; SUWEN ZHU; BEIJIU CHENG (Journal of Genetics, 2014)

A circulatory system useful both for long-term somatic embryogenesis and genetic transformation in Vitis vinifera L. cv. Thompson Seedless - Qi Zhou; Lingmin Dai; Siyan Cheng; Jing He; Dan Wang; Jianxia Zhang; Yuejin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Responses of soil micronutrient availability to experimental warming in two contrasting forest ecosystems in the Eastern Tibetan Plateau, China - Dan-Dan Li; Yue-Jiao Li; Jin Liang; Chun-Zhang Zhao; Hua-Jun Yin; Chun-Ying Yin; Xin-Ying Cheng; Qing Liu (Journal of Soils and Sediments, 2014)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Residential energy consumption and associated carbon emission in forest rural area in China: A case study in Weichang County - Fei Lun; Josep G. Canadell; Zhong-qi Xu; Lu He; Zheng Yuan; Dan Zhang; Wen-hua Li; Mou-cheng Liu (Journal of Mountain Science, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Effect of BRAF V600E mutation on tumor response of anti-EGFR monoclonal antibodies for first-line metastatic colorectal cancer treatment: a meta-analysis of randomized studies - Dandan Cui; Dan Cao; Yu Yang; Meng Qiu; Ying Huang; Cheng Yi (Molecular Biology Reports, 2014)

Diversity Analysis of Bacterial Community from Permafrost Soil of Mo-he in China - Dong Dan; Dian-peng Zhang; Wei-cheng Liu; Cai-ge Lu; Tao-tao Zhang (Indian Journal of Microbiology, 2014)

Cloning and functional analysis of a novel ascorbate peroxidase (APX) gene from Anthurium andraeanum - Hui-chun Liu; Dan-qing Tian; Jian-xin Liu; Guang-ying Ma; Qing-cheng Zou; Zhu-jun Zhu (Journal of Zhejiang University-SCIENCE B, 2013)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Isolation of two new D ehalococcoides mccartyi strains with dissimilar dechlorination functions and their characterization by comparative genomics via microarray analysis - Patrick K. H. Lee; Dan Cheng; Kimberlee A. West; Lisa Alvarez‐Cohen; Jianzhong He (Environmental Microbiology, 2013)
Summary Microbial reductive dechlorination of trichloroethene ( TCE ) in groundwater often results in the accumulation of dichloroethenes ( DCE s). D ehalococcoides mccartyi ( D hc ) are the only known bacteria capable of dechlorination beyond DCE to non‐toxic ethene. In this study, two newly isolated D hc strains (11a and 11a5) with dissimilar functional abilities are described. Strain 11a reductively dechlorinates TCE , 1,1‐ DCE , cis ‐ DCE , trans ‐ DCE , and vinyl chloride ( VC ) to ethene, while strain 11a5 dechlorinates TCE and all three DCE isomers only to VC . Each of these dechlorination reactions are coupled to growth by these strains. The VC dechlorination rate of strain 11a occurs at a rate of 258 nmol per min per mg of protein, about two times faster than previously reported stains. Strain 11a possesses the vcrA gene while strain 11a5 contains the tceA gene. Strains 11a and 11a5 share 100% 16 S rRNA gene sequence identity with previously sequenced D hc strains BAV1 and CBDB1 , placing it within the P inellas subgroup, and 85.4% and 89.5% of all genes present in the CBDB1 and BAV1 genomes were detected in strains 11a and 11a5, respectively, using a custom‐designed microarray targeting four sequenced D hc strains. Genes that were not detected in strains 11a and 11a5 are mostly within the high plasticity regions or integrated elements of the sequenced strains. This study reports the functional description and comparative genomics of two additional D hc isolates and provides evidence that the observed functional incongruence between the activity and core genome phylogenies of D hc strains is likely driven by the horizontal transfer of key reductive dehalogenase‐encoding genes.

Complete disassociation of adult pancreas into viable single cells through cold trypsin-EDTA digestion - Dan Li; Shi-yun Peng; Zhen-wu Zhang; Rui-cheng Feng; Lu Li; Jie Liang; Sheng Tai; Chun-bo Teng (Journal of Zhejiang University-SCIENCE B, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Fine mapping of a major flowering time QTL on soybean chromosome 6 combining linkage and association analysis - Dan Zhang; Hao Cheng; Zhenbin Hu; Hui Wang; Guizheng Kan; Chunying Liu; Deyue Yu (Euphytica, 2013)

Differential autophagic cell death under stress with ectopic cytoplasmic and mitochondrial-specific PPP2R2B in human neuroblastoma cells - Kang Fang; Hui-Fang Li; Chang-Heng Hsieh; Dan-Yu Li; Ding-Chieh Song; Wan-Ting Cheng; Zhi-Xuan Guo (Apoptosis, 2013)

Expression of survivin and patients survival in non-small cell lung cancer: a meta-analysis of the published studies - Li-nian Huang; Dong-sheng Wang; Yu-qing Chen; Cheng-ling Zhao; Bei-lei Gong; An-bang Jiang; Wei Jia; Feng-dan Hu (Molecular Biology Reports, 2013)

Erratum to: Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Duu-Jong Lee; Aijie Wang (Environmental Science and Pollution Research, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

The propagule supply, litter layers and canopy shade in the littoral community influence the establishment and growth of Myriophyllum aquaticum - Dong Xie; Dan Yu; Wen-Hua You; Cheng-Xing Xia (Biological Invasions, 2013)

Quinolinoneacetic acid derivatives as novel glutathione S-transferase P1-1 inhibitors: insights into the interaction modes by molecular modeling - Jian Wang; Shao-Jie Wang; Dan-Dan Song; Yong-Kui Jing; Mao-Sheng Cheng (Medicinal Chemistry Research, 2012)

Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Aijie Wang (Environmental Science and Pollution Research, 2012)

Identification of single nucleotide polymorphisms and haplotypes associated with yield and yield components in soybean (Glycine max) landraces across multiple environments - Derong Hao; Hao Cheng; Zhitong Yin; Shiyou Cui; Dan Zhang; Hui Wang; Deyue Yu (Theoretical and Applied Genetics, 2012)

Effects of Raingauge Distribution on Estimation Accuracy of Areal Rainfall - Chun-dan Cheng; Shin-jen Cheng; Jet-chau Wen; Ju-huang Lee (Water Resources Management, 2012)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Bioavailability, mobility, and toxicity of Cu in soils around the Dexing Cu mine in China - Guangyong Guo; Tao Yuan; Wenhua Wang; Dan Li; Jinping Cheng; Yang Gao; Pei Zhou (Environmental Geochemistry and Health, 2011)

Microcalorimetric study of the effect of Benzoinum and Styrax on the growth of Escherichia coli - Jian Wang; Danhong Cheng; Nan Zeng; Houlin Xia; Yong Fu; Dan Yan; Yanling Zhao; Xiaohe Xiao (Natural Product Research, 2011)

Diversity and paleobiogeographic distribution patterns of early and Middle Ordovician graptolites in distinct depositional environments of South China - YuanDong Zhang; Xu Chen; Goldman Dan; Ju Zhang; JunFeng Cheng; YanYan Song (Science China Earth Sciences, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

An ethanol inducible alc system for regulating gene expression in Beauveria bassiana - Xing-gang Liao; Yong-jun Zhang; Yan-hua Fan; Jin-cheng Ma; Yong-hong Zhou; Dan Jin; Yan Pei (World Journal of Microbiology and Biotechnology, 2009)

Quercetin inhibits IL-1 beta-induced ICAM-1 expression in pulmonary epithelial cell line A549 through the MAPK pathways - Binwu Ying; Ting Yang; Xingbo Song; Xiaobo Hu; Hong Fan; Xiaojun Lu; Lijuan Chen; Deyun Cheng; Tao Wang; Daishun Liu; Dan Xu; Yuquan Wei; et al. (Molecular Biology Reports, 2009)

Detection of quantitative trait loci for phosphorus deficiency tolerance at soybean seedling stage - Dan Zhang; Hao Cheng; Leiyue Geng; Guizhen Kan; Shiyou Cui; Qingchang Meng; Junyi Gai; Deyue Yu (Euphytica, 2009)

Elevated β1,4-galactosyltransferase-I induced by the intraspinal injection of lipopolysaccharide - Aiguo Shen; Jianping Chen; Ji Qian; Jianchun Zhu; Ling Hu; Meijuan Yan; Dan Zhou; Ying Gao; Junling Yang; Fei Ding; Chun Cheng (Glycoconjugate Journal, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

Inhibitory Effect of Copper Complex of Indomethacin on Bacteria Studied by Microcalorimetry - Yang Chang-Ying; Liu Yi; Zhu Jun-Cheng; Zheng Dan (Biological Trace Element Research, 2008)

Characterization of novel microsatellite loci in rare minnow (Gobiocypris rarus) and amplification in closely related species in Gobioninae - Xiaolin Liao; Dan Wang; Xiaomu Yu; Weitao Li; Lei Cheng; Jianwei Wang; Jingou Tong (Conservation Genetics, 2007)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)